Responses of understory plant diversity to fire regimes in temperate forests - Sarita Chaulagain; Sabine Kasel; Trent D. Penman; Lauren T. Bennett (Forest Ecology and Management, 2026)

Watershed Continuum Monitoring Approach: combining multiple water quality patterns along stream and river flowpaths to track sources, pathways, and processing of pollutants - Sujay S. Kaushal; Ashley E. Mon; Stanley B. Grant; Paul M. Mayer; Aaron J. Porter; Andrew J. Sekellick; Jason H. Chase; Shantanu V. Bhide; John D. Jastram; Tamara A. Newcomer-Johnson; Sydney A. Shelton; Alexis M. Yaculak; et al. (Ecological Engineering, 2026)

Gestational exposure to organophosphate ester flame retardants and child growth in weight, height, and body mass index at age 2-10 years: the Environmental influences on Child Health Outcomes Program - Anne P. Starling; Xuan Li; Jennifer L. Ames; Emily S. Barrett; Theresa M. Bastain; Claudia Buss; Dana Dabelea; Anne L. Dunlop; Assiamira Ferrara; Monique M. Hedderson; Julie Herbstman; Kurunthachalam Kannan; et al. (Environmental Research, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

A critical review of potential modifiers of air pollutant associations with dementia and related outcomes - JeongWon Han; Yina Li; Sangji Lee; Katie M. Lynch; Erin E. Bennett; Qi Ying; Eun Sug Park; Richard L. Smith; James D. Stewart; Eric A. Whitsel; Melinda C. Power; Xiaohui Xu (NeuroToxicology, 2026)

Characterising Ecosystem Composition, Structure and Function of Alternative Stable States in Temperate Forests of South‐Eastern Australia - Aaron E. Heap; Tom A. Fairman; Trent D. Penman; Lauren T. Bennett (Global Change Biology, 2026)
Increasingly frequent and intense wildfires threaten to push ecosystems beyond their ecological thresholds. Fire‐adapted forests can be vulnerable to ecosystem conversion under shortening fire‐return intervals. To evaluate the impacts of fire regime change, we contrasted Eucalyptus forests that retained canopy cover under tolerable regimes (reference forests) with alternative states of markedly reduced canopy. These alternative states established following short‐interval wildfires and have persisted through subsequent fires. Alternative states were dominated by more uniform distributions of small trees ( 20 cm diameter). These changes in structure translated into declines in several key ecosystem functions. The loss of large, hollow‐forming trees and limited Eucalyptus regeneration indicate long‐term constraints on habitat availability for hollow‐dependent fauna. Coarse woody debris mass was 38% lower in alternative states, indicating decreased resources for detritivores, fungi, and ground‐dwelling mammals. Aboveground carbon stocks were reduced by 59%, with a much higher proportion (98%) stored in small trees than reference states (20%). Lower fire tolerance of small trees suggests a greater vulnerability of carbon stocks to subsequent fires in alternative states compared to reference states. These findings highlight the long‐term ecological consequences of altered fire regimes. In addition, emphasising the management and restoration of forest structural integrity is essential to maintain ecosystem functions in fire‐prone landscapes that are increasingly vulnerable under changing climates.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Weaving nostalgia into sense of place: Linking memory, identity, and land in working landscapes - Zubair Barkat; Jessica D. Ulrich-Schad; Elizabeth A. Bennett; Madison Brunell (Rangelands, 2026)

Chronic exposure to waterborne nickel significantly reduced growth of juvenile crayfish (Faxonius virilis) - Adrian P. Moore; Mark L. Wildhaber; Zachary D. Beaman; Kendell R. Bennett; Karlie K. Ditter; Danielle Cleveland; Jenna A. Blanton; Tyler J. Grant (Ecotoxicology, 2026)

Integration of Indigenous practices into fisheries legislation: Obstacles and opportunities for the maramataka (Māori lunar calendar) - Louise Bennett-Jones; Christopher D. Hepburn; Brendan Flack; Nigel J. Scott; Gaya Gnanalingam (Marine Policy, 2026)

Hooking injury, physiological stress, and post-release activity patterns of giant trevally (Caranx ignobilis) captured using spinning gear in a catch-and-release recreational fishery - Andy J. Danylchuk; Luc LaRochelle; Graham D. Raby; Brian Bennett; Steven J. Cooke; Jacob W. Brownscombe (Environmental Biology of Fishes, 2026)

Fertility classification of the cow and peri-estrus sex-steroid hormones is associated with endometrial epithelial cell responses to conceptus and inflammatory signals - Cecilia Constantino Rocha; Mariangela Bueno Cordeiro Maldonado; Fernando S. Mesquita; Alexandra Bennett; Abdul Waheed; Graciana R. Mendina; Gabriela Lomba Dasqueve; Felipe A. C. C. Silva; Marcelo Fábio Gouveia Nogueira; Alan D. Ealy; Thomas Hansen; Mario Binelli (Cell and Tissue Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Bomb radiocarbon reveals keratin growth dynamics in loggerhead (Caretta caretta) and green (Chelonia mydas) turtles - Bethan Linscott; Amy A. Wallace; Lorena Becerra-Valdivia; Matt R. P. Harris; Alexandra L. Fireman; Jenna D. Bennett; William F. Patterson; Hannah B. Vander Zanden (Marine Biology, 2026)
Incrementally formed biological tissues can serve as archives of biochemical information pertaining to the life histories of organisms. The sequential isotopic analysis of marine turtle scute keratin is increasingly used for ecological reconstruction, but the timescales represented by these tissues remain poorly understood. Here, we present a method to establish scute growth rates using sequential radiocarbon ( 14 C) measurements on samples taken from loggerhead ( Caretta caretta ) and green turtles ( Chelonia mydas ) stranded along the Florida coast. Using a Δ 14 C coral-otolith reference series and a Bayesian modelling approach, we reconstructed the rate of keratin formation in 24 individuals (representing 120 radiocarbon measurements) and detected synchronous declines in scute growth rates that may be linked to marine environmental stress. Our results provide a chronological framework for the ecological interpretation of biogeochemical data from green and loggerhead turtle scutes and demonstrate the potential for 14 C analysis to investigate the growth dynamics of other incremental tissues.

Metabolic cost of external work: a novel CPET parameter optimises characterisation of exercise performance in obese individuals - Jennifer J. Rayner; Rebecca R. Chamley; Robert Barker Davies; Oliver O’Sullivan; Peter Ladlow; Alex N. Bennett; Edward D. Nicol; Oliver J. Rider; David A. Holdsworth (European Journal of Applied Physiology, 2026)
Purpose Both obesity and cardiorespiratory fitness are crucial determinants of symptoms and prognosis. However, interpreting the gold-standard cardiopulmonary exercise test (CPET) is complicated by increasing body size and varying body composition. We hypothesised that the ‘metabolic cost of external work’ (or oxygen uptake (ml/min)/workload (Watts); V̇O 2 /W), a body weight-independent determinant of endurance capacity, would reflect metabolic health more accurately than V̇O 2 alone. Methods A test cohort of 160 fit individuals underwent anthropomorphic and metabolic assessment, maximal bicycle ergometer CPET, and six-minute walk test (6MWT). V̇O 2 /W was calculated at VT1 and peak. The performance of V̇O 2 /W was validated in 62 older, less fit individuals, undergoing the same protocol. 24 obese volunteers were assigned a weight loss intervention, and the impact on V̇O 2 /W examined. Results In both test and validation cohort, V̇O 2 /W at VT1 and peak correlated with 6MWT distance, more strongly than standard CPET parameters. Including V̇O 2 /W improved the accuracy of predicting 6MWT distance. V̇O 2 /W correlated with BMI, insulin sensitivity and waist-to-hip ratio. Metabolic cost falls with weight loss, in parallel to metabolic and functional improvements, in contrast to other CPET parameters. Conclusion Metabolic cost is strongly associated with functional capacity and metabolic health across a range of body weight and fitness, outperforming standard CPET metrics. It is a simple measure which may improve our assessment of the extent to which exertional symptoms are determined by metabolic factors in an individual, and thereby target the most appropriate intervention to those who will benefit most. Graphical Abstract

Acute Toxicity of 6PPDQ, 6PPD, and Other Transformation Products to a Freshwater Mussel (Lampsilis siliquoidea, Barnes 1823) - David J. Soucek; Rebecca A. Dorman; Jeffery A. Steevens; Viviane Yargeau; Marco Pineda; Christopher D. Metcalfe; Erin R. Bennett (Bulletin of Environmental Contamination and Toxicology, 2026)

Molecular taxonomy of the guitarfish genus Acroteriobatus (Rhinopristiformes: Rhinobatidae) - Mia J. Groeneveld; Juliana D. Klein; Michaela van Staden; Rhett H. Bennett; Matthew L. Dicken; David A. Ebert; Bruce Q. Mann; Kashmika Perumal; Ralph G. A. Watson; Aletta E. Bester-van der Merwe (Marine Biodiversity, 2026)
Guitarfish species (genus Acroteriobatus ) display restricted distributions in undermanaged regions of intense fishing pressure. The importance of accurate specimen identification is well established, especially in the context of conservation management. However, guitarfishes remain poorly understood, which is exacerbated by taxonomic uncertainty due to morphological similarity. We therefore aimed (1) to identify molecular operational taxonomic units (MOTUs) within Acroteriobatus by analysing sampled specimens as well as publicly available sequence data for the cytochrome c oxidase subunit I ( COI ) and nicotinamide adenine dehydrogenase subunit 2 (ND2 ) genes, and (2) to augment and review the representation of these sequences on public databases. A molecular taxonomic approach integrating species delimitation and specimen assignment methods revealed 14 MOTUs. These MOTUs aligned with current species descriptions, displaying no evidence of cryptic diversity. Both genes demonstrated similar interspecific relationships that broadly reflected current distribution ranges, underscoring sub-regional endemism. Moreover, discrepancies in public sequence repositories were identified, attributed to misidentified specimens and the usage of outdated taxonomic nomenclature. Genetic diversity indices were substantially inflated when specimens were grouped based on reported species versus delimited MOTUs, thus overestimating genetic diversity. We highlight the need for extensive, curated DNA reference libraries, including revising earlier sequence entries in light of new taxonomic insights, to enable reliable identification of morphologically conserved species. The molecular resolution illustrated in this study can aid in clarifying taxonomic uncertainties in the genus Acroteriobatus .

Spatial and temporal variations in the distribution of eastern Australian post-orogenic granites and related mineral deposits: metallogenic and tectonic significance - D. L. Huston; Y. Cheng; S. L. Jones; D. C. Champion; M. D. Norman; M. W. Agnew; A. Cross; V. C. Bennett; R. A. Creaser (Australian Journal of Earth Sciences, 2026)

Overriding influence of climate on future carbon stocks in Australian temperate forests - Bianca J. Pickering; Denis Kultaev; Craig R. Nitschke; Erica Marshall; Dan Ababei; Trent D. Penman; Lauren T. Bennett (Science of The Total Environment, 2026)

Food limitation erodes the thermal tolerance of larvae in an ecologically influential marine herbivore - Maya J. Munstermann; Sam E. Karelitz; Rachele Ferraro; Laura Rogers‐Bennett; Rachel D. Simons; Daniel K. Okamoto (Ecology, 2026)
Biologists often use organismal thermal tolerance to help explain or forecast responses of populations to climate change. Yet many studies quantify thermal tolerance under isolated laboratory conditions despite extreme events, such as heatwaves, often coinciding with other stressors such as nutrient or food limitation. These oversights may be consequential as recent theory suggests thermal tolerance itself can be fundamentally altered by food limitation. Here, we experimentally test how food limitation (500–10,000 cells mL −1 ) affects long‐term survival, development, and growth across a present‐day range of temperatures (10–20°C) in the most sensitive life stages of an important marine herbivore, purple sea urchins ( Strongylocentrotus purpuratus ). We show food limitation substantially erodes thermal tolerance in terms of survival, but when provided ample food, larvae exhibited robust survival across temperatures currently experienced by larvae in nature. Reductions in food however lowered optimal survival temperatures and shifted survival thresholds to those conditions observed during recent marine heatwaves. These results are consistent with the “metabolic meltdown” hypothesis—shifting optima and upper limits to cooler temperatures—and illustrate how present‐day warming coupled with lower productivity may lead to substantial, unexpected declines in larval survival and recruitment. In contrast to survival, developmental rates and time to metamorphic competency, which ranged from 21 to 61 days, were driven largely by temperature with little impact of food concentration. Our findings relate to historical observations of declines in larval supply at the southern edge of the species range. Overall, these results have broad‐reaching implications beyond sea urchin populations as sea urchin herbivory is known to control productivity of kelp forest communities. We provide evidence of how laboratory derived thermal reaction norms can be coupled with ecologically relevant food concentrations to inform unexpected vital rate declines of sensitive life stages in a changing climate.

Catch trends and population status of the leopard whipray Himantura leoparda (family Dasyatidae) off the east coast of South Africa - BQ Mann; R Daly; D Parker; GL Jordaan; G Cliff; N Nkabi; R Kyle; R Bennett (African Journal of Marine Science, 2025)

Association of midlife air pollution and road proximity exposure with 29-year cognitive decline - Melinda C. Power; Ziwei Song; Annie Chen; Katie M. Lynch; Naa Adoley Parker-Allotey; Erin E. Bennett; Xiaohui Xu; Eric A. Whitsel; Richard L. Smith; James D. Stewart; Eun Sug Park; Qi Ying; et al. (NeuroToxicology, 2025)

BMP9 knockout impairs pulmonary vessel muscularisation and confers aberrant tamoxifen sensitivity - Benjamin J. Dunmore; Stephen Moore; Rowena J. Jones; Joshua Hodgson; Kathryn Auckland; Mark Southwood; Nichola Figg; Nobuhiro Kikuchi; Martin Bennett; Allan Lawrie; Christopher J. Rhodes; Mark R. Toshner; et al. (Angiogenesis, 2025)
Deleterious mutations in the GDF2 gene, encoding BMP9, are causative of pulmonary arterial hypertension and hereditary haemorrhagic telangiectasia. Paradoxically, BMP9 germ-line knockout ( Gdf2 −/− ; Bmp9 KO) and double Bmp9 KO / conditional Bmp10 cKO (dKO) mice exhibit an attenuated response to PAH-inducing stimuli. We asked whether this contradiction is due to the pathological, physiological, or genetic consequences of BMP9 knockout. In Bmp9 KO mice we observed reduced pulmonary vascular smooth muscle cell (SMC) coverage and using RNA-seq analysis of Bmp9 KO mouse lungs identified two novel genes, COLQ and ITGA6 , which were differentially regulated in a human PAH RNA-seq dataset. In order to study BMP10 loss, postnatal tamoxifen treatment was required to induce Bmp10 cKO. As previously reported, in dKO mice we observed cardiomegaly and splenomegaly, as well as hyperplasia and hemosiderosis in the pulmonary vasculature. Surprisingly, tamoxifen treated Bmp9 KO control mice phenocopied these pathological changes in dKO mice and downregulated SMC marker gene transcription. Loss of BMP10 is not critical for severe tissue remodelling in the lung, heart, and spleen, rather Bmp9 KO mice appear sensitive to tamoxifen and BMP9 loss is the primary cause of mild vessel remodelling due to a basal reduction of smooth muscle cell coverage. This study suggests that interaction of the BMP pathway with tamoxifen needs to be carefully considered when studying Bmp9 KO mice and urges caution in the context of tamoxifen use when studying cardiovascular and pulmonary disease models.

Pre- and post-move exposure to air pollution and neighborhood socioeconomic status - Chelsea Liu; Erin E. Bennett; Katie M. Lynch; Xiaohui Xu; Eun Sug Park; Qi Ying; Richard L. Smith; James D. Stewart; Eric A. Whitsel; Joel D. Kaufman; Emma K. Stapp; Melinda C. Power (Science of The Total Environment, 2025)

Appearance Pressure From the Media Mediates the Relationship Between Internalized Weight Bias and Eating Disorder Risk for Young Women: A Cross-Sectional Study - Brooke L. Bennett; Allison F. Wagner; Rachel D. Marshall; Janet D. Latner (Journal of the Academy of Nutrition and Dietetics, 2025)

Towards identifying the economically optimum sampling density for variable-rate soil constraint management - S. D. Roberton; J. McL. Bennett; C. R. Lobsey; T. F. A. Bishop (Precision Agriculture, 2025)
The investment in soil sampling is often disproportionate to the level of investment for soil amelioration. While advanced geostatistical Digital Soil Mapping (DSM) methods exist to map spatially variable soils, they are rarely used in precision agriculture, due to the increased soil sampling requirement, the cost of which is perceived as prohibitive. Consequently, soil constraints are regularly managed on blanket-rate basis, where a single rate is applied across spatial variable soils. What sampling density is required to deploy these methods in practice, and can an increased investment in soil sampling enable more economically optimised soil amelioration? This paper presents a method to answer this question in Australian broadacre agriculture. The method, which seeks to identify the economically optimum sampling density, is tested on a 100 ha broadacre grain field in Central NSW, Australia. Sampling densities ranging from 0.1 to 3 samples per ha are tested, through observing the accuracy of gypsum recommendations as a practice to treat sodic soils. A status quo Blanket-rate (BR) approach is tested against DSM via the deployment of ordinary kriging to create continuous variable-rate (VR) recommendations. Application errors are assessed both in terms of cost of over-applied product, as well as lost yield potentialy due to under-application. While for this test site, an economically optimum sampling density of 1 core per 5 ha and 1 core per 2 ha for 0–20 cm topsoil management and 0–60 cm profile management was identified, we propose the development Nopt function. Development of this function would allow for optimum sampling investments to be estimated at new sites, in consideration to the inherent site variability and the economic magnitude of soil amelioration. Through development of this function and it’s applied example in this paper, we seek to develop the value proposition for increased soil data collection in Australian Agriculture.

Acute exposure to water from the Chicago area waterway system induces molecular indices of stress and disturbance in silver carp: implications for deterrence to range expansion - Amy E. Schneider; Andrew J. Bennett; Clark E. Dennis; Andrew. J. Esbaugh; James T. Lamer; Cory D. Suski (Biological Invasions, 2025)
Exposure of an animal to sub-optimal habitat can result in impairment, damage or increased energy expenditure to maintain homeostasis, which can direct resources away from reproduction and reduce fitness. Animals may therefore avoid sub-optimal habitats to minimize physiological costs. Silver carp ( Hypophthalmichthys molitrix ) are a prolific invader in the Mississippi River basin. Despite their propensity for spread, the ‘leading edge’ of silver carp at the northern limit of their distribution in the Illinois River has stalled and not advanced for over a decade. Studies have suggested that contaminants in the Chicago Area Waterway System (CAWS) may be deterring upstream range expansion, but this hypothesis has had limited testing to date. The current study sought to quantify linkages between CAWS water constituents and impaired range expansion of silver carp. For this, CAWS water from beyond the current upstream distribution of silver carp was collected and transported downstream to the core of the population. Silver carp from the population core were collected and exposed to either water from their collection location (control), or to CAWS water from upstream of the current distribution, simulating range expansion. Following exposure, olfactory and liver tissue were collected to quantify genetic expression and histological indices of damage. Results showed that silver carp olfactory tissue experienced increased activity of genes related to xenobiotic defense and oxidative stress following exposure to CAWS water from upstream of the current distribution, highlighting costs associated with inhabiting this environment, providing a role for contaminants in CAWS water at deterring further upstream movement.

Genome-wide associations within diverse wild apple germplasm for postharvest blue mold resistance to Penicillium expansum - Lauren Whitt; John S. Bennett; Tamara D. Collum; Breyn Evans; Doug Raines; Ben Gutierrez; Wojciech J. Janisiewicz; Wayne M. Jurick; Christopher Gottschalk (Postharvest Biology and Technology, 2025)

Human sperm as an in vitro toxicity model: a versatile tool for assessing the risk of environmental contaminants - Shannen Keyser; Daniel Marcu; Morgan T. D. Davidse; Monique Bennett; Leslie Petrik; Liana Maree (Archives of Toxicology, 2025)
Contaminants of emerging concern (CECs) pose a significant threat to human and ecosystem health due to their persistence, bioaccumulation in higher trophic levels, and potential toxicity. While in vivo models are commonly used for toxicity screening, developing alternative in vitro techniques for rapid environmental risk assessment is essential. Spermatozoa, with their compartmentalized structure, measurable characteristics and sensitivity to environmental changes, offer potential as an in vitro model for toxicity screening. We evaluated the impact of selected CECs, including pharmaceuticals and pesticides, on sperm function in highly motile sperm subpopulations selected from donor semen. Standardised protocols were applied to assess various sperm functional parameters after 1–4 h of exposure to either individual or a mixture of chemicals. Our findings revealed that total motility is insufficient to detect subtle toxic effect. More responsive measures, such as sperm kinematics, induced hyperactivation, viability, mitochondrial membrane potential (MMP) and presence of reactive oxygen species (ROS) should be assessed to elucidate the effect of a toxic environment on sperm function. Most chemicals exerted a dose–response effect on sperm parameters, with the higher concentrations resulting in the most negative effects. The inherent sensitivity of human spermatozoa to oxidative stress, mitochondrial damage and energy metabolism, makes them a robust model for assessing toxicity. These features highlight their utility as an alternative cellular model for evaluating CECs and advancing risk assessment methodologies.

Fostering equity: How welcomeness, safety, and representation influence visitor coping and intention-to-return to parks and protected areas - Sammie L. Powers; Lauren A. Ferguson; Michael D. Ferguson; Semra Aytur; Mark B. Gorman; Jessie L. Bennett; Eric Feldbaum (Journal of Outdoor Recreation and Tourism, 2025)

Short-interval fires homogenise the structure of diverse temperate forests - Aaron E. Heap; Trent D. Penman; Lauren T. Bennett; Thomas A. Fairman (Forest Ecology and Management, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Metabolic Insights Into Microbially Induced Calcite Formation by Bacillaceae for Application in Bio‐Based Construction Materials - Michael Seidel; Charlotte Hamley‐Bennett; Bianca J. Reeksting; Manpreet Bagga; Lukas Hellmann; Timothy D. Hoffmann; Christiane Kraemer; Irina Dana Ofiţeru; Kevin Paine; Susanne Gebhard (Environmental Microbiology, 2025)
Microbially induced calcite precipitation (MICP) offers promising solutions for sustainable, low‐cement infrastructure materials. While it is known how urea catabolism leads to biomineralisation, the non‐ureolytic pathways of MICP are less clear. This limits the use of the latter in biotechnology, despite its clear benefit of avoiding toxic ammonia release. To address this knowledge gap, the present study explored the interdependence between carbon source utilisation and non‐ureolytic MICP. We show that acetate can serve as the carbon source driving calcite formation in several environmental Bacillaceae isolates. This effect was particularly clear in a Solibacillus silvestris strain, which could precipitate almost all provided calcium when provided with a 2:1 acetate‐to‐calcium molar ratio, and we show that this process was independent of active cell growth. Genome sequencing and gene expression analyses revealed an apparent link between acetate catabolism and calcite precipitation in this species, suggesting MICP may be a calcium stress response. Development of a simple genetic system for S. silvestris led to the deletion of a proposed calcium binding protein, although this showed minimal effects on MICP. Taken together, this study provides insights into the physiological processes leading to non‐ureolytic MICP, paving the way for targeted optimisation of biomineralisation for sustainable materials development.

An improved method for quantitatively measuring antifouling coating performance using a mussel single thread tensile adhesion test - Samuel M. Pennell; Thomas B. LeFevre; Jonathan Bennett; Wilaiwan Chouyyok; Joseph D. Daddona; Raymond S. Addleman; Curtis J. Larimer; George T. Bonheyo (Biofouling, 2025)

Latitudinal gradients in herbivorous and detritivorous reef fish productivity - Sterling B. Tebbett; Helen F. Yan; Scott Bennett; Graham J. Edgar; Scott D. Ling; Rick D. Stuart-Smith; David R. Bellwood (Reviews in Fish Biology and Fisheries, 2025)

Occurrence of mobulid rays in Northwest Madagascar - Stella Diamant; Caterina Bosio; Joshua Rambahiniarison; Chris Scarffe; Michel Strogoff; Jeremy J. Kiszka; Rhett Bennett; Tanguy Guillemain d’Echon; Elina Sourisseau; Léonce C. M. Fidiarisandratra; Salvatore Cerchio; Stephanie Venables; et al. (Environmental Biology of Fishes, 2025)
The waters around Nosy Be in northwest Madagascar are well-known for the occurrence of large planktivores, such as whale sharks ( Rhincodon typus ) and Omura’s whales ( Balaenoptera omurai ). Between 2016 and 2022, sighting data on mobulid rays were opportunistically collected during tourism activities. Additional sources, including citizen science submissions, tourism operator reports, and social media records, were used to compile sightings of three mobulid ray species. A total of 255 encounters were documented, with Mobula mobular ( n = 165) being the most common, followed by M. birostris ( n = 60) and M. kuhlii ( n = 30). Notably, the absence of confirmed M. alfredi records since 2015 suggests a potential local decline. This study highlights Nosy Be as a habitat for mobulid rays and emphasises the necessity for further species monitoring, ongoing identification of potential threats, and management initiatives aiming at reducing mortality from gillnet fishing.

Prenatal exposure to environmental bisphenols over time and their association with childhood asthma, allergic rhinitis and atopic dermatitis in the ECHO consortium - Rachel L. Miller; Yuyan Wang; Jenny Aalborg; Akram N. Alshawabkeh; Deborah H. Bennett; Carrie V. Breton; Jessie P. Buckley; Dana Dabelea; Anne L. Dunlop; Assiamira Ferrara; Griffith Gao; Abigail Gaylord; et al. (Environmental Pollution, 2025)

Novel Curvularia species causing disseminated phaeohyphomycosis in a dog - Jared A. Jaffey; Connie F. Cañete-Gibas; Nathan P. Wiederhold; Carmita J. Sanders; Jason D. Struthers; Annalise Black; BinXi Wu; Kara S. Thomas; Patricia Bennett; Jessica Watt (Topics in Companion Animal Medicine, 2025)

Fractionation of complex aromatic hydrocarbon mixtures using membrane cascades hybridized with distillation - Young Joo Lee; Hye Youn Jang; Bennett D. Marshall; Mohammed I.L. Abutaqiya; Neel Rangnekar; Nicholas C. Bruno; M.G. Finn; Ryan P. Lively (Chemical Engineering Journal, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Stuck in the mangrove mud: The risk of trace element exposure to shore crabs in restored urban mangroves - Jasmine A. Rasmussen; William W. Bennett; Steve D. Melvin; Michael Sievers; Charlotte A. McAneney; Ainsley Leaning; Rod M. Connolly (Science of The Total Environment, 2024)

The effects of estuarine outflows on coastal marine ecosystems in New South Wales, Australia - J.A. Rasmussen; T. Ingleton; W.W. Bennett; R.M. Pearson; McAneney CA; E. Foulsham; D. Hanslow; P.R. Scanes; R.M. Connolly (Marine Pollution Bulletin, 2024)

Long-term evolution of the Sulzberger Ice Shelf, West Antarctica: Insights from 74-year observations and 2022 Hunga-Tonga volcanic tsunami-induced calving - Aiguo Zhao; Yuan Cheng; Alexander D. Fraser; Luke G. Bennetts; Haifeng Xiao; Qi Liang; Teng Li; Rongxing Li (Earth and Planetary Science Letters, 2024)

From land to sea: Environmental DNA is correlated with long-term water quality indicators in an urbanized estuary - Adam T. Downie; William W. Bennett; Shaun Wilkinson; Mark de Bruyn; Joseph D. DiBattista (Marine Pollution Bulletin, 2024)

Can green firebreaks help balance biodiversity, carbon storage and wildfire risk? - Erica Marshall; Brendan Holyland; Kate Parkins; Elisa Raulings; Megan K. Good; Matthew Swan; Lauren T. Bennett; Trent D. Penman (Journal of Environmental Management, 2024)

Dynamic modeling of geological carbon storage in aquifers – workflows and practices - Seyyed A. Hosseini; Reza Ershadnia; Lisa Lun; Stephen Morgan; Matthew Bennett; Chris Skrivanos; Boxiao Li; Mohamad Reza Soltanian; Rajesh Pawar; Susan D. Hovorka (International Journal of Greenhouse Gas Control, 2024)

Association of midlife air pollution exposures and residential road proximity with incident dementia: The Atherosclerosis Risk in Communities (ARIC) study - Ziwei Song; Katie Lynch; Naa Adoley Parker-Allotey; Erin E. Bennett; Xiaohui Xu; Eric A. Whitsel; Richard Smith; James D. Stewart; Eun Sug Park; Qi Ying; Melinda C. Power (Environmental Research, 2024)

Diesel exhaust particle extract elicits an oxPAPC-like transcriptomic profile in macrophages across multiple mouse strains - May Bhetraratana; Luz D. Orozco; Brian J. Bennett; Karla Luna; Xia Yang; Aldons J. Lusis; Jesus A. Araujo (Environmental Pollution, 2024)

Testing a rapid assessment approach for estimating ecosystem service capacity in urban green alleys - Marie C. Dade; Isabella C. Richmond; Jesse T. Rieb; Erin T.H. Crockett; Kayleigh Hutt-Taylor; Serena Sinno; Karina Benessaiah; Catherine Destrempes; Jacqueline Hamilton; Fatemeh Izadi; L. Emily Kroft; Lingshan Li; et al. (Urban Forestry & Urban Greening, 2024)

Fisheries and the COVID-19 pandemic: A global scoping review of the early pressures, impacts, and responses in least developed, emerging, and developed countries - Richard A. Nyiawung; Taylor Ehrlick; Nathan J. Bennett; Nicolas D. Brunet; Fabio Matos; Cristina Pita; Joshua S. Stoll; Philip A. Loring (Regional Studies in Marine Science, 2024)

A comparison of PM2.5 exposure estimates from different estimation methods and their associations with cognitive testing and brain MRI outcomes - Melinda C. Power; Katie M. Lynch; Erin E. Bennett; Qi Ying; Eun Sug Park; Xiaohui Xu; Richard L. Smith; James D. Stewart; Jeff D. Yanosky; Duanping Liao; Aaron van Donkelaar; Joel D. Kaufman; et al. (Environmental Research, 2024)

Perspectives: Five organizing themes for invasive forest insect and disease management in Canada and the United States - Emma J. Hudgins; Brian Leung; Chris J.K. MacQuarrie; Deborah G. McCullough; Abraham Francis; Gary M. Lovett; Qinfeng Guo; Kevin M. Potter; Catherine I. Cullingham; Frank H. Koch; Jordanna N. Bergman; Allison D. Binley; et al. (Forest Ecology and Management, 2024)

Longitudinal relationships between depressive symptoms, functional impairment, and physical activity in later late life - Lisa Y. Xiong; Madeline Wood Alexander; Hugo Cogo-Moreira; Che-Yuan Wu; Michael Eid; Nathan Herrmann; Damien Gallagher; Jodi D. Edwards; Krista L. Lanctôt; Susan Marzolini; David A. Bennett; Jennifer S. Rabin; et al. (GeroScience, 2024)

Endangered giant kelp forests support similar fish and macroinvertebrate communities to sympatric stipitate kelp forests - Hunter Forbes; Elisabeth M. A. Strain; Scott Bennett; Scott D. Ling; Cayne Layton (Biodiversity and Conservation, 2024)
Kelp forests provide habitat for many species, but it remains uncertain whether specific kelp forest types support distinct biodiversity. Surface canopy-forming giant kelp ( Macrocystis pyrifera ) forests in Tasmania, Australia, have declined significantly due to climate change, and have been widely replaced by forests dominated by smaller stipitate kelps like Ecklonia radiata . However, there is limited knowledge of the community composition of Macrocystis forests and how this may differ from the stipitate kelp forest community. Underwater visual census surveys were conducted of the fishes and macroinvertebrates (> 2.5 cm length) in remnant Macrocystis forests in south-eastern Tasmania, and in adjacent stipitate kelp forests. 18 sites (9 of each forest type) were surveyed across two regions during the period of peak growth and canopy cover (i.e. winter-spring). Faunal community composition varied little between forest types, although Macrocystis forests supported more than double the abundance and biomass of mobile fishes, while cryptic fishes differed by forest type depending on region. Macroinvertebrate assemblages did not differ between forest types nor regions. Thus, for the taxa and time period examined, Tasmanian Macrocystis and stipitate kelp forests supported mostly similar faunal communities. Kelp forest communities showed spatial variation and were also likely influenced by a variety of other habitat characteristics, such as the relatively small patch sizes and/or ephemeral state of the remnant Macrocystis forests. Quantifying the community structure of these endangered communities informs the ecological changes that have occurred and will serve as an important reference for ongoing conservation and restoration activities.

Sustainable coffee: A review of the diverse initiatives and governance dimensions of global coffee supply chains - Dale R. Wright; Sarah A. Bekessy; Pia E. Lentini; Georgia E. Garrard; Ascelin Gordon; Amanda D. Rodewald; Ruth E. Bennett; Matthew J. Selinske (Ambio, 2024)
With a global footprint of 10 million hectares across 12.5 million farms, coffee is among the world’s most traded commodities. The coffee industry has launched a variety of initiatives designed to reduce coffee’s contribution to climate change and biodiversity loss and enhance the socio-economic conditions of coffee producers. We systematically reviewed the literature on the sustainability and governance of coffee production and developed a typology of eleven sustainability initiatives. Our review shows that coffee sustainability research has focused primarily on the economic outcomes of certification schemes. The typology expands our knowledge of novel sustainability initiatives being led by coffee farming communities themselves, allowing for an improved consideration of power dynamics in sustainability governance. Sustainability initiatives governed by local actors can improve sustainability outcomes by empowering local decision makers to assess direct risks and benefits of sustainable practices to the local environment, economy, and culture.

Composite substrates for coral larval settlement and reef restoration based on natural hydraulic lime and inorganic strontium and magnesium compounds - J. Yus; E.N. Nixon; J. Li; J. Noriega Gimenez; M-J. Bennett; D. Flores; K.L. Marhaver; L. Wegley Kelly; R.M. Espinosa-Marzal; A.J. Wagoner Johnson (Ecological Engineering, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

The future of gender research in small‐scale fisheries: Priorities and pathways for advancing gender equity - Emma D. Rice; Edith Gondwe; Abigail E. Bennett; Patrick Asango Okanga; Nimah F. Osho‐Abdulgafar; Kafayat Fakoya; Ayodele Oloko; Sarah Harper; Patrick Chimseu Kawaye; Ernest O. Chuku; Hillary Smith (Fish and Fisheries, 2024)
This paper presents an agenda for the future of gender research in small‐scale fisheries (SSF). Building on expert insight from scholars who gathered during the 4th World Small‐Scale Fisheries Congress Africa (4WSFC) with a synthesis of existing literature, we identify six topics that warrant future investigation in SSF, along with methodological considerations for addressing them. Research priorities include identifying pathways towards (1) equitable participation in governance and decision‐making, (2) valuing all actors' contributions to aquatic food systems, (3) increasing access to financial services, (4) inclusive infrastructural development, (5) livelihood diversification and (6) reducing occupational health hazards. Several important methodological considerations include (i) using multiple methodologies, (ii) applying participatory methods, (iii) collecting gender‐disaggregated data, (iv) integrating gender into a food systems approach in fisheries, (v) engaging an intersectional approach and (vi) operationalising equity.

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Single-molecule analysis of purified proteins and nuclear extracts: Insights from 8-oxoguanine glycosylase 1 - Matthew A. Schaich; Tyler M. Weaver; Vera Roginskaya; Bret D. Freudenthal; Bennett Van Houten (DNA Repair, 2024)

Assessing impacts of a notorious invader (common carp Cyprinus carpio) on Australia's aquatic ecosystems: Coupling abundance-impact relationships with a spatial biomass model - Benjamin G. Fanson; Robin Hale; Jason D. Thiem; Jarod P. Lyon; John D. Koehn; Andrew F. Bennett; Ivor Stuart (Biological Conservation, 2024)

Minimum-entropy velocity estimation from GPS position time series - Jarir Saleh; Richard A. Bennett; Simon D. P. Williams (Journal of Geodesy, 2024)

New Zealand rickettsia‐like organism and Tenacibaculum maritimum vaccine efficacy study - D. Jaramillo; B. P. Busby; M. Bestbier; P. Bennett; Z. Waddington (Journal of Fish Diseases, 2024)
A cohort of Chinook salmon juveniles was vaccinated, with an autogenous bivalent vaccine against New Zealand RLOs (NZ‐RLO1) and Tenacibaculum maritimum. A proportion of the cohort was not vaccinated to act as controls. At smoltification, the fish were challenged with NZ‐RLO1, NZ‐RLO2, or T. maritimum . We found that challenge with T. maritimum by immersion in (7.5 × 10 5 cfu/mL of water) did not yield any pathology. Challenge with RLOs produced clinical signs that were more or less severe depending on the challenge route, dose or vaccination status. Survival was significantly higher for vaccinated fish within the groups challenged with NZ‐RLO1 by intraperitoneal injection with a relative percent survival (RPS) of 48.84%. Survival was not significantly different between vaccinated and non‐vaccinated fish for groups challenged with NZ‐RLO2 by intraperitoneal injection or by NZ‐RLO1 by immersion. Yet, anecdotally the clinical disease presentation (manifesting as haemorrhagic, ulcerative skin lesions) was more severe for the non‐vaccinated fish. This study demonstrates that autogenous vaccine against NZ‐RLO is protective against severe disease and death by NZ‐RLO1 challenge which warrants implementation and further evaluation under field conditions. Yet, this study also highlights the importance of the route of administration and dose when evaluating pathogenicity and vaccine efficacy.

Effects of temperature and microbial disruption on juvenile kelp Ecklonia radiata and its associated bacterial community - Sebastian Vadillo Gonzalez; Catriona L. Hurd; Damon Britton; Eloise Bennett; Peter D. Steinberg; Ezequiel M. Marzinelli (Frontiers in Marine Science, 2024)
Ocean warming can affect the development and physiological responses of kelps, and under future climate change scenarios, increasing seawater temperatures pose a major threat to these habitat-forming species. However, little is known about the effects of warming on epiphytic bacterial communities and how an altered microbiome may interact with temperature stress, affecting the condition and survival of kelp, particularly of the potentially more vulnerable early life stages. Here, we tested the effects of thermal stress on the growth and physiological responses of juvenile kelp Ecklonia radiata in which their epiphytic bacterial community was experimentally disrupted using antimicrobials, simulating dysbiosis. We hypothesized that, under thermal stress (23°C, simulating a extreme scenario of ocean warming in Tasmania), kelp with a disrupted bacterial community would be more strongly affected than kelp with an undisrupted microbiome or kelp under ambient temperature (14°C) but with a disrupted microbiota. Thermal stress reduced growth, increased tissue bleaching and negatively affected net photosynthesis of kelp. In addition, a substantial change in the epiphytic bacterial community structure was also found under thermal stress conditions, with an increase in the abundance of potentially pathogenic bacterial groups. However, microbial disruption did not act synergistically with thermal stress to affect kelp juveniles. These results suggest that effects of elevated temperature on juvenile kelps is not microbially-mediated and that juveniles may be less susceptible to disruptions of their microbiome.

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

Harnessing water fleas for water reclamation: A nature-based tertiary wastewater treatment technology - Muhammad Abdullahi; Iestyn Stead; Sophie Bennett; Rafael Orozco; Mohamed Abou-Elwafa Abdallah; Sara Jabbari; Lynne E. Macaskie; Alexandra Tzella; Stefan Krause; Bushra Al-Duri; Robert G. Lee; Ben Herbert; et al. (Science of The Total Environment, 2023)

Beyond here and now: Evaluating pollution estimation across space and time from street view images with deep learning - Ricky Nathvani; Vishwanath D.; Sierra N. Clark; Abosede S. Alli; Emily Muller; Henri Coste; James E. Bennett; James Nimo; Josephine Bedford Moses; Solomon Baah; Allison Hughes; Esra Suel; et al. (Science of The Total Environment, 2023)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

Effects of short-chain per- and polyfluoroalkyl substances (PFAS) on toxicologically relevant gene expression profiles in a liver-on-a-chip model - Megan E. Solan; Bennett Schackmuth; Erica D. Bruce; Sahar Pradhan; Christie M. Sayes; Ramon Lavado (Environmental Pollution, 2023)

Influence of cross-scale measures on neighborhood resilience - Kyle D. Buck; Rebecca J. Dunn; Mary K. Bennett; Justin J. Bousquin (Natural Hazards, 2023)

The biology of an isolated Mashona mole-rat population from southern Malawi, with implications for the diversity and biogeography of the genus Fukomys - R. Šumbera; M. Uhrová; S. Begall; K. R. Caspar; D. Jerkovičová; P. Van Daele; W. N. Chitaukali; C. G. Faulkes; N. C. Bennett; C. Johannes; H. Burda; O. Mikula (Organisms Diversity & Evolution, 2023)
The Mashona mole-rat, Fukomys darlingi (Thomas, 1895), is a little studied social African mole-rat (Bathyergidae) from south-astern Africa. Here, we present an integrative study characterizing the genetic diversity of populations assigned to F. darlingi with special focus on animals from Nsanje, southern Malawi. These mole-rats show pronounced differences in body mass and general appearance compared to nominate F. darlingi from Zimbabwe and Mozambique, but their taxonomic status has so far remained unclear. A genetic analysis encompassing all major lineages of the genus Fukomys suggests that this population indeed represents a deeply nested lineage within the F. darlingi clade . The karyotype of the Nsanje mole-rats also corresponds to that of the nominate form, being 2n = 54. While both nuclear and mitochondrial data agree about the assignment of the Nsanje mole-rats to F. darlingi , our analyses revealed substantial mitonuclear discordance for other branches within the Fukomys phylogenetic tree. Nsanje mole-rats are significantly larger than nominate F. darlingi and their ontogeny and reproduction closely resemble similar-sized congeneric species rather than the nominate population. The somatic growth of the Nsanje form is the slowest of all African mole-rats. The maximum life span of F. darlingi is at least 19 years. The observed differences between nominate F. darlingi and mole-rats from Nsanje may be attributed mainly to their different body mass. Our study highlights the advantages of an integrative approach for understanding the diversity of African mole-rats and emphasizes the great intraspecific variability that may be encountered in these underground-dwelling rodents.

Valorisation strategies for brown seaweed biomass production in a European context - Joseph P. Bennett; Laura F. Robinson; Leonardo D. Gomez (Algal Research, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

The IV International Symposium on Fungal Stress and the XIII International Fungal Biology Conference - Alene Alder-Rangel; Alexandre Melo Bailão; Alfredo Herrera-Estrella; Amanda E.A. Rangel; Attila Gácser; Audrey P. Gasch; Claudia B.L. Campos; Christina Peters; Francine Camelim; Fulvia Verde; Geoffrey Michael Gadd; Gerhard Braus; et al. (Fungal Biology, 2023)

Protected area planning to conserve biodiversity in an uncertain future - Richard Schuster; Rachel Buxton; Jeffrey O. Hanson; Allison D. Binley; Jeremy Pittman; Vivitskaia Tulloch; Frank A. La Sorte; Patrick R. Roehrdanz; Peter H. Verburg; Amanda D. Rodewald; Scott Wilson; Hugh P. Possingham; et al. (Conservation Biology, 2023)
Protected areas are a key instrument for conservation. Despite this, they are vulnerable to risks associated with weak governance, land‐use intensification, and climate change. We used a novel hierarchical optimization approach to identify priority areas for expanding the global protected area system that explicitly accounted for such risks while maximizing protection of all known terrestrial vertebrate species. To incorporate risk categories, we built on the minimum set problem, where the objective is to reach species distribution protection targets while accounting for 1 constraint, such as land cost or area. We expanded this approach to include multiple objectives accounting for risk in the problem formulation by treating each risk layer as a separate objective in the problem formulation. Reducing exposure to these risks required expanding the area of the global protected area system by 1.6% while still meeting conservation targets. Incorporating risks from weak governance drove the greatest changes in spatial priorities for protection, and incorporating risks from climate change required the largest increase (2.52%) in global protected area. Conserving wide‐ranging species required countries with relatively strong governance to protect more land when they bordered nations with comparatively weak governance. Our results underscore the need for cross‐jurisdictional coordination and demonstrate how risk can be efficiently incorporated into conservation planning. Planeación de las áreas protegidas para conservar la biodiversidad en un futuro incierto

Chow diet in mouse aging studies: nothing regular about it - Jennifer Lee; Chloe Purello; Sarah L. Booth; Brian Bennett; Christopher D. Wiley; Ron Korstanje (GeroScience, 2023)
Chow diet is used in the majority of rodent studies and, although assumed to be standardized for dietary source and nutritional contents, it varies widely across commercial formulations. Similarly, current approaches to study aging in rodents involve a single-diet formulation across the lifespan and overlook age-specific nutritional requirements, which may have long-term effects on aging processes. Together, these nutrition-based disparities represent major gaps in geroscience research, affecting the interpretation and reproducibility of the studies. This perspective aims to raise awareness on the importance of rodent diet formulation and proposes that geroscientists include detailed descriptions of all experimental diets and feeding protocols. Detailed reporting of diets will enhance rigor and reproducibility of aging rodent studies and lead to more translational outcomes in geroscience research.

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

Angiotensin receptor blocker use is associated with upregulation of the memory-protective angiotensin type 4 receptor (AT4R) in the postmortem brains of individuals without cognitive impairment - Caglar Cosarderelioglu; Lolita S. Nidadavolu; Claudene J. George; Ruth Marx-Rattner; Laura Powell; Qian-Li Xue; Jing Tian; Esther S. Oh; Luigi Ferrucci; Pervin Dincer; David A. Bennett; Jeremy D. Walston; et al. (GeroScience, 2023)

A global biological conservation horizon scan of issues for 2023 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Holly M. Butterworth; Mick N. Clout; Isabelle M. Côté; Jason Dinsdale; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice Hughes; et al. (Trends in Ecology & Evolution, 2023)

Polymorphism of the follicle stimulating hormone receptor does not impact reproductive performance or in-vitro embryo production in beef heifers - Alexandria P. Snider; Hannah K. Yake; Camryn D. Granger; Shelby L. Rosasco; Tara G. McDaneld; Warren M. Snelling; Chad C. Chase; Jeremy R. Miles; Clay A. Lents; Lacey K. Quail; Jerica J.J. Rich; Kaitlin M. Epperson; et al. (Theriogenology, 2023)

Multi-year evaluation of muskellunge (Esox masquinongy) spatial ecology during winter drawdowns in a regulated, urban waterway in Canada - Jordanna N. Bergman; Kate L. Neigel; Sean J. Landsman; Danny Glassman; Luc LaRochelle; Joseph R. Bennett; Colin D. Rennie; Jesse C. Vermaire; Steven J. Cooke (Hydrobiologia, 2023)

Vulnerable Waters are Essential to Watershed Resilience - Charles R. Lane; Irena F. Creed; Heather E. Golden; Scott G. Leibowitz; David M. Mushet; Mark C. Rains; Qiusheng Wu; Ellen D’Amico; Laurie C. Alexander; Genevieve A. Ali; Nandita B. Basu; Micah G. Bennett; et al. (Ecosystems, 2023)
Watershed resilience is the ability of a watershed to maintain its characteristic system state while concurrently resisting, adapting to, and reorganizing after hydrological (for example, drought, flooding) or biogeochemical (for example, excessive nutrient) disturbances. Vulnerable waters include non-floodplain wetlands and headwater streams, abundant watershed components representing the most distal extent of the freshwater aquatic network. Vulnerable waters are hydrologically dynamic and biogeochemically reactive aquatic systems, storing, processing, and releasing water and entrained (that is, dissolved and particulate) materials along expanding and contracting aquatic networks. The hydrological and biogeochemical functions emerging from these processes affect the magnitude, frequency, timing, duration, storage, and rate of change of material and energy fluxes among watershed components and to downstream waters, thereby maintaining watershed states and imparting watershed resilience. We present here a conceptual framework for understanding how vulnerable waters confer watershed resilience. We demonstrate how individual and cumulative vulnerable-water modifications (for example, reduced extent, altered connectivity) affect watershed-scale hydrological and biogeochemical disturbance response and recovery, which decreases watershed resilience and can trigger transitions across thresholds to alternative watershed states (for example, states conducive to increased flood frequency or nutrient concentrations). We subsequently describe how resilient watersheds require spatial heterogeneity and temporal variability in hydrological and biogeochemical interactions between terrestrial systems and down-gradient waters, which necessitates attention to the conservation and restoration of vulnerable waters and their downstream connectivity gradients. To conclude, we provide actionable principles for resilient watersheds and articulate research needs to further watershed resilience science and vulnerable-water management.

CW198 acts as a genetic insulator to block enhancer-promoter interaction in plants - Li Jiang; Yue Liu; Zhifeng Wen; Yingjun Yang; Stacy D. Singer; Dennis Bennett; Wenying Xu; Zhen Su; Zhifang Yu; Josh Cohn; Xi Luo; Zhongchi Liu; et al. (Transgenic Research, 2022)

Rank change and growth within social hierarchies of the orange clownfish, Amphiprion percula - L. M. Fitzgerald; H. B. Harrison; D. J. Coker; P. Sáenz-Agudelo; M. Srinivasan; J. E. Majoris; L. Boström Einarsson; B. Pujol; M. Bennett-Smith; S. R. Thorrold; S. Planes; G. P. Jones; et al. (Marine Biology, 2022)
Social hierarchies within groups define the distribution of resources and provide benefits that support the collective group or favor dominant members. The progression of individuals through social hierarchies is a valuable characteristic for quantifying population dynamics. On coral reefs, some clownfish maintain size-based hierarchical communities where individuals queue through social ranks. The cost of waiting in a lower-ranked position is outweighed by the reduced risk of eviction and mortality. The orange clownfish, Amphiprion percula , maintains stable social groups with subordinate individuals queuing to be part of the dominant breeding pair. Strong association with their host anemone, complex social interactions, and relatively low predation rates make them ideal model organisms to assess changes in group dynamics through time in their natural environment. Here, we investigate the rank changes and isometric growth rates of A. percula from 247 naturally occurring social groups in Kimbe Island, Papua New Guinea (5° 12′ 13.54″ S, 150° 22′ 32.69″ E). We used DNA profiling to assign and track individuals over eight years between 2011 and 2019. Over half of the individuals survived alongside two or three members of their original social group, with twelve breeding pairs persisting over the study period. Half of the surviving individuals increased in rank and experienced double the growth rate of those that maintained their rank. Examining rank change in a wild fish population provides new insights into the complex social hierarchies of reef fishes and their role in social evolution.

Nitrogen and Sulfur Deposition Reductions Projected to Partially Restore Forest Soil Conditions in the US Northeast, While Understory Composition Continues to Shift with Future Climate Change - Stephen D. LeDuc; Christopher M. Clark; Jennifer Phelan; Salim Belyazid; Micah G. Bennett; Katie Boaggio; John Buckley; Jamie Cajka; Phillip Jones (Water, Air, & Soil Pollution, 2022)

The fuel–climate–fire conundrum: How will fire regimes change in temperate eucalypt forests under climate change? - Sarah C. McColl‐Gausden; Lauren T. Bennett; Hamish G. Clarke; Dan A. Ababei; Trent D. Penman (Global Change Biology, 2022)
Fire regimes are changing across the globe in response to complex interactions between climate, fuel, and fire across space and time. Despite these complex interactions, research into predicting fire regime change is often unidimensional, typically focusing on direct relationships between fire activity and climate, increasing the chances of erroneous fire predictions that have ignored feedbacks with, for example, fuel loads and availability. Here, we quantify the direct and indirect role of climate on fire regime change in eucalypt dominated landscapes using a novel simulation approach that uses a landscape fire modelling framework to simulate fire regimes over decades to centuries. We estimated the relative roles of climate‐mediated changes as both direct effects on fire weather and indirect effects on fuel load and structure in a full factorial simulation experiment (present and future weather, present and future fuel) that included six climate ensemble members. We applied this simulation framework to predict changes in fire regimes across six temperate forested landscapes in south‐eastern Australia that encompass a broad continuum from climate‐limited to fuel‐limited. Climate‐mediated change in weather and fuel was predicted to intensify fire regimes in all six landscapes by increasing wildfire extent and intensity and decreasing fire interval, potentially led by an earlier start to the fire season. Future weather was the dominant factor influencing changes in all the tested fire regime attributes: area burnt, area burnt at high intensity, fire interval, high‐intensity fire interval, and season midpoint. However, effects of future fuel acted synergistically or antagonistically with future weather depending on the landscape and the fire regime attribute. Our results suggest that fire regimes are likely to shift across temperate ecosystems in south‐eastern Australia in coming decades, particularly in climate‐limited systems where there is the potential for a greater availability of fuels to burn through increased aridity.

Using the Resist‐Accept‐Direct management framework to respond to climate‐driven transformations in marine ecosystems - Laura Rogers‐Bennett; Gabrielle Yang; Jordan D. Mann (Fisheries Management and Ecology, 2022)
Climate change is impacting natural ecosystems and the services they provide at an unprecedented rate, yet management is not keeping pace with radical ecosystem transformations. Management in marine systems is primarily designed to regulate fishing pressures, which may be of limited use in addressing large‐scale climate impacts. The Resist‐Accept‐Direct (RAD) is a flexible, novel framework that gives managers a way to structure and plan how to respond to radical shifts/transformations in ecosystems. We present marine case studies of broad scale impacts and outline how the responses may fit into the RAD concept. We use the RAD framework to address the collapse of the kelp forest in northern California and examine how potential policy guiding restoration strategies can be organised. We conclude that the response to most marine ecosystem transformations has been to use the resist strategy that includes adaptive management, and we suggest that for the kelp forests in California the resist strategy provides the best option for moving forward. The RAD framework will be useful for marine ecosystem transformations in which systems have reached their tipping points and now require novel restoration tools and thinking as we face climate change stressors and an unpredictable future.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

A Scientific Synthesis of Marine Protected Areas in the United States: Status and Recommendations - Jenna Sullivan-Stack; Octavio Aburto-Oropeza; Cassandra M. Brooks; Reniel B. Cabral; Jennifer E. Caselle; Francis Chan; J. Emmett Duffy; Daniel C. Dunn; Alan M. Friedlander; Heather K. Fulton-Bennett; Steven D. Gaines; Leah R. Gerber; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are a key tool for achieving goals for biodiversity conservation and human well-being, including improving climate resilience and equitable access to nature. At a national level, they are central components in the U.S. commitment to conserve at least 30% of U.S. waters by 2030. By definition, the primary goal of an MPA is the long-term conservation of nature; however, not all MPAs provide the same ecological and social benefits. A U.S. system of MPAs that is equitable, well-managed, representative and connected, and includes areas at a level of protection that can deliver desired outcomes is best positioned to support national goals. We used a new MPA framework, The MPA Guide, to assess the level of protection and stage of establishment of the 50 largest U.S. MPAs, which make up 99.7% of the total U.S. MPA area (3.19 million km 2 ). Over 96% of this area, including 99% of that which is fully or highly protected against extractive or destructive human activities, is in the central Pacific ocean. Total MPA area in other regions is sparse – only 1.9% of the U.S. ocean excluding the central Pacific is protected in any kind of MPA (120,976 km 2 ). Over three quarters of the non-central Pacific MPA area is lightly or minimally protected against extractive or destructive human activities. These results highlight an urgent need to improve the quality, quantity, and representativeness of MPA protection in U.S. waters to bring benefits to human and marine communities. We identify and review the state of the science, including focal areas for achieving desired MPA outcomes and lessons learned from places where sound ecological and social design principles come together in MPAs that are set up to achieve national goals for equity, climate resilience, and biodiversity conservation. We recommend key opportunities for action specific to the U.S. context, including increasing funding, research, equity, and protection level for new and existing U.S. MPAs.

Does bait type and bait container configuration influence the performance of remote underwater video systems in temperate freshwater lakes for assessing fish community structure? - D. M. Glassman; A. Chhor; J. C. Vermaire; J. R. Bennett; S. J. Cooke (Hydrobiologia, 2022)

Tracking the early stages of an invasion with biotelemetry: behaviour of round goby (Neogobius melanostomus) in Canada’s historic Rideau Canal - Jordanna N. Bergman; Graham D. Raby; Kate L. Neigel; Colin D. Rennie; Sigal Balshine; Joseph R. Bennett; Aaron T. Fisk; Steven J. Cooke (Biological Invasions, 2022)

Persistent thermally driven shift in the functional trait structure of herbivorous fishes: Evidence of top‐down control on the rebound potential of temperate seaweed forests? - Nestor E. Bosch; Matthew McLean; Salvador Zarco‐Perello; Scott Bennett; Rick D. Stuart‐Smith; Adriana Vergés; Albert Pessarrodona; Fernando Tuya; Tim Langlois; Claude Spencer; Sahira Bell; Benjamin J. Saunders; et al. (Global Change Biology, 2022)
Extreme climatic events can reshape the functional structure of ecological communities, potentially altering ecological interactions and ecosystem functioning. While these shifts have been widely documented, evidence of their persistence and potential flow‐on effects on ecosystem structure following relaxation of extreme events remains limited. Here, we investigate changes in the functional trait structure – encompassing dimensions of resource use, thermal affinity, and body size – of herbivorous fishes in a temperate reef system that experienced an extreme marine heatwave (MHW) and subsequent return to cool conditions. We quantify how changes in the trait structure modified the nature and intensity of herbivory‐related functions (macroalgae, turf, and sediment removal), and explored the potential flow‐on effects on the recovery dynamics of macroalgal foundation species. The trait structure of the herbivorous fish assemblage shifted as a result of the MHW, from dominance of cool‐water browsing species to increased evenness in the distribution of abundance among temperate and tropical guilds supporting novel herbivory roles (i.e. scraping, cropping, and sediment sucking). Despite the abundance of tropical herbivorous fishes and intensity of herbivory‐related functions declined following a period of cooling after the MHW, the underlying trait structure displayed limited recovery. Concomitantly, algal assemblages displayed a lack of recovery of the formerly dominant foundational species, the kelp Ecklonia radiata , transitioning to an alternative state dominated by turf and Sargassum spp. Our study demonstrates a legacy effect of an extreme MHW and exemplified the value of monitoring phenotypic (trait mediated) changes in the nature of core ecosystem processes to predict and adapt to the future configurations of changing reef ecosystems.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - R. J. Longchamps; S. Y. Yang; C. A. Castellani; W. Shi; J. Lane; M. L. Grove; T. M. Bartz; C. Sarnowski; C. Liu; K. Burrows; A. L. Guyatt; T. R. Gaunt; et al. (Human Genetics, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes ( p = 3.09 × 10 –15 ) and the gene ontology (GO) terms for mtDNA metabolism ( p = 1.43 × 10 –8 ) and mtDNA replication ( p = 1.2 × 10 –7 ). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall ( p = 0.044) and non-cancer mortality ( p = 6.56 × 10 –4 ).

The ten steps to responsible Inland fisheries in practice: reflections from diverse regional case studies around the globe - Steven J. Cooke; Elizabeth Nyboer; Abigail Bennett; Abigail J. Lynch; Dana M. Infante; Ian G. Cowx; T. Douglas Beard; Devin Bartley; Craig P. Paukert; Andrea J. Reid; Simon Funge-Smith; Edith Gondwe; et al. (Reviews in Fish Biology and Fisheries, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Global assessment of marine and freshwater recreational fish reveals mismatch in climate change vulnerability and conservation effort - Elizabeth A. Nyboer; Hsien‐Yung Lin; Joseph R. Bennett; Joseph Gabriel; William Twardek; Auston D. Chhor; Lindsay Daly; Sarah Dolson; Eric Guitard; Peter Holder; Christina M. Mozzon; Alexandria Trahan; et al. (Global Change Biology, 2021)
Recreational fisheries contribute substantially to the sociocultural and economic well‐being of coastal and riparian regions worldwide, but climate change threatens their sustainability. Fishery managers require information on how climate change will impact key recreational species; however, the absence of a global assessment hinders both directed and widespread conservation efforts. In this study, we present the first global climate change vulnerability assessment of recreationally targeted fish species from marine and freshwater environments (including diadromous fishes). We use climate change projections and data on species’ physiological and ecological traits to quantify and map global climate vulnerability and analyze these patterns alongside the indices of socioeconomic value and conservation effort to determine where efforts are sufficient and where they might fall short. We found that over 20% of recreationally targeted fishes are vulnerable to climate change under a high emission scenario. Overall, marine fishes had the highest number of vulnerable species, concentrated in regions with sensitive habitat types (e.g., coral reefs). However, freshwater fishes had higher proportions of species at risk from climate change, with concentrations in northern Europe, Australia, and southern Africa. Mismatches in conservation effort and vulnerability were found within all regions and life‐history groups. A key pattern was that current conservation effort focused primarily on marine fishes of high socioeconomic value rather than on the freshwater and diadromous fishes that were predicted to be proportionately more vulnerable. While several marine regions were notably lacking in protection (e.g., Caribbean Sea, Banda Sea), only 19% of vulnerable marine species were without conservation effort. By contrast, 72% of freshwater fishes and 33% of diadromous fishes had no measures in place, despite their high vulnerability and cultural value. The spatial and taxonomic analyses presented here provide guidance for the future conservation and management of recreational fisheries as climate change progresses.

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Limited Progress in Improving Gender and Geographic Representation in Coral Reef Science - Gabby N. Ahmadia; Samantha H. Cheng; Dominic A. Andradi-Brown; Stacy K. Baez; Megan D. Barnes; Nathan J. Bennett; Stuart J. Campbell; Emily S. Darling; Estradivari; David Gill; Erika Gress; Georgina G. Gurney; et al. (Frontiers in Marine Science, 2021)
Despite increasing recognition of the need for more diverse and equitable representation in the sciences, it is unclear whether measurable progress has been made. Here, we examine trends in authorship in coral reef science from 1,677 articles published over the past 16 years (2003–2018) and find that while representation of authors that are women (from 18 to 33%) and from non-OECD nations (from 4 to 13%) have increased over time, progress is slow in achieving more equitable representation. For example, at the current rate, it would take over two decades for female representation to reach 50%. Given that there are more coral reef non-OECD countries, at the current rate, truly equitable representation of non-OECD countries would take even longer. OECD nations also continue to dominate authorship contributions in coral reef science (89%), in research conducted in both OECD (63%) and non-OECD nations (68%). We identify systemic issues that remain prevalent in coral reef science (i.e., parachute science, gender bias) that likely contribute to observed trends. We provide recommendations to address systemic biases in research to foster a more inclusive global science community. Adoption of these recommendations will lead to more creative, innovative, and impactful scientific approaches urgently needed for coral reefs and contribute to environmental justice efforts.

Topically delivered 22 nt siRNAs enhance RNAi silencing of endogenous genes in two species - Bill Hendrix; Wei Zheng; Matthew J. Bauer; Ericka R. Havecker; Jennifer T. Mai; Paul H. Hoffer; Rick A. Sanders; Brian D. Eads; Amy Caruano-Yzermans; Danielle N. Taylor; Chelly Hresko; Janette Oakes; et al. (Planta, 2021)
Main conclusion 22 nt siRNAs applied to leaves induce production of transitive sRNAs for targeted genes and can enhance local silencing. Systemic silencing was only observed for a GFP transgene. Abstract RNA interference (RNAi) is a gene silencing mechanism important in regulating gene expression during plant development, response to the environment and defense. Better understanding of the molecular mechanisms of this pathway may lead to future strategies to improve crop traits of value. An abrasion method to deliver siRNAs into leaf cells of intact plants was used to investigate the activities of 21 and 22 nt siRNAs in silencing genes in Nicotiana benthamiana and Amaranthus cruentus . We confirmed that both 21 and 22 nt siRNAs were able to silence a green fluorescent protein ( GFP ) transgene in treated leaves of N. benthamiana , but systemic silencing of GFP occurred only when the guide strand contained 22 nt. Silencing in the treated leaves of N. benthamiana was demonstrated for three endogenous genes: magnesium cheletase subunit I ( CHL-I ), magnesium cheletase subunit H ( CHL-H ), and GENOMES UNCOUPLED4 (GUN4) . However, systemic silencing of these endogenous genes was not observed. Very high levels of transitive siRNAs were produced for GFP in response to treatment with 22 nt siRNAs but only low levels were produced in response to a 21 nt siRNA. The endogenous genes tested also produced transitive siRNAs in response to 22 nt siRNAs. 22 nt siRNAs produced greater local silencing phenotypes than 21 nt siRNAs for three of the genes. These special properties of 22 nt siRNAs were also observed for the CHL-H gene in A. cruentus . These experiments suggest a functional role for transitive siRNAs in amplifying the RNAi response.

Connectivity of Large-Bodied Fish with a Recovering Estuarine Tidal Marsh, Revealed Using an Imaging Sonar - Mark A. Bennett; Alistair Becker; Troy Gaston; Matthew D. Taylor (Estuaries and Coasts, 2021)

Pandora: 4-D White Matter Bundle Population-Based Atlases Derived from Diffusion MRI Fiber Tractography - Colin B Hansen; Qi Yang; Ilwoo Lyu; Francois Rheault; Cailey Kerley; Bramsh Qamar Chandio; Shreyas Fadnavis; Owen Williams; Andrea T. Shafer; Susan M. Resnick; David H. Zald; Laurie E Cutting; et al. (Neuroinformatics, 2021)

Incidence and risk factors for respiratory tract bacterial colonization and infection in lung transplant recipients - L. Paglicci; V. Borgo; N. Lanzarone; M. Fabbiani; C. Cassol; MG. Cusi; M. Valassina; S. Scolletta; E. Bargagli; L. Marchetti; P. Paladini; L. Luzzi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
To evaluate incidence of and risk factors for respiratory bacterial colonization and infections within 30 days from lung transplantation (LT). We retrospectively analyzed microbiological and clinical data from 94 patients transplanted for indications other than cystic fibrosis, focusing on the occurrence of bacterial respiratory colonization or infection during 1 month of follow-up after LT. Thirty-three percent of patients developed lower respiratory bacterial colonization. Bilateral LT and chronic heart diseases were independently associated to a higher risk of overall bacterial colonization. Peptic diseases conferred a higher risk of multi-drug resistant (MDR) colonization, while longer duration of aerosol prophylaxis was associated with a lower risk. Overall, 35% of lung recipients developed bacterial pneumonia. COPD (when compared to idiopathic pulmonary fibrosis, IPF) and higher BMI were associated to a lower risk of bacterial infection. A higher risk of MDR infection was observed in IPF and in patients with pre-transplant colonization and infections. The risk of post-LT respiratory infections could be stratified by considering several factors (indication for LT, type of LT, presence of certain comorbidities, and microbiologic assessment before LT). A wider use of early nebulized therapies could be useful to prevent MDR colonization, thus potentially lowering infectious risk.

Come together: calibration of tiger shark (Galeocerdo cuvier) microsatellite databases for investigating global population structure and assignment of historical specimens - M. Sort; A. Manuzzi; B. Jiménez-Mena; J. R. Ovenden; B. J. Holmes; A. M. Bernard; M. S. Shivji; D. Meldrup; M. B. Bennett; E. E. Nielsen (Conservation Genetics Resources, 2021)

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

Integrated metabolomics reveals altered lipid metabolism in adipose tissue in a model of extreme longevity - Justin Darcy; Yimin Fang; Samuel McFadden; Matthew D. Lynes; Luiz O. Leiria; Jonathan M. Dreyfuss; Valerie Bussburg; Vladimir Tolstikov; Bennett Greenwood; Niven R. Narain; Michael A. Kiebish; Andrzej Bartke; et al. (GeroScience, 2020)

Three lessons conservation science can learn from the COVID‐19 pandemic - Rachel T. Buxton; Jordanna N. Bergman; Hsien‐Yung Lin; Allison D. Binley; Stephanie Avery‐Gomm; Richard Schuster; Dominique G. Roche; Joseph R. Bennett (Conservation Biology, 2020)
Article impact statement : COVID‐19 has demonstrated the need to optimize research activity, convey the gravity of loss, and reevaluate merit in conservation science.

Spatial and temporal patterns of lateralization in a parrot species complex - Mathew L. Berg; Sarah A. Micallef; Justin R. Eastwood; Raoul F. H. Ribot; Andrew T. D. Bennett (Evolutionary Ecology, 2020)

Climate change and adaptation to social-ecological change: the case of indigenous people and culture-based fisheries in Sri Lanka - Eranga K. Galappaththi; James D. Ford; Elena M. Bennett (Climatic Change, 2020)

The COVID-19 Pandemic, Small-Scale Fisheries and Coastal Fishing Communities - Nathan J. Bennett; Elena M. Finkbeiner; Natalie C. Ban; Dyhia Belhabib; Stacy D. Jupiter; John N. Kittinger; Sangeeta Mangubhai; Joeri Scholtens; David Gill; Patrick Christie (Coastal Management, 2020)

Central adiposity at diagnosis may reduce prostate cancer-specific mortality in African-Caribbean men with prostate cancer: 10-year follow-up of participants in a case–control study - Maria D. Jackson; Marshall K. Tulloch-Reid; Affette M. McCaw-Binns; William Aiken; Trevor S. Ferguson; Nadia R. Bennett; Leroy Harrison; Asha Badaloo; Donovan McGrowder; Annielle Grindley; Evelyn Walker; Simon G. Anderson (Cancer Causes & Control, 2020)

The Bacillus anthracis class Ib ribonucleotide reductase subunit NrdF intrinsically selects manganese over iron - Kristīne Grāve; Julia J. Griese; Gustav Berggren; Matthew D. Bennett; Martin Högbom (JBIC Journal of Biological Inorganic Chemistry, 2020)
Correct protein metallation in the complex mixture of the cell is a prerequisite for metalloprotein function. While some metals, such as Cu, are commonly chaperoned, specificity towards metals earlier in the Irving–Williams series is achieved through other means, the determinants of which are poorly understood. The dimetal carboxylate family of proteins provides an intriguing example, as different proteins, while sharing a common fold and the same 4-carboxylate 2-histidine coordination sphere, are known to require either a Fe/Fe, Mn/Fe or Mn/Mn cofactor for function. We previously showed that the R2lox proteins from this family spontaneously assemble the heterodinuclear Mn/Fe cofactor. Here we show that the class Ib ribonucleotide reductase R2 protein from Bacillus anthracis spontaneously assembles a Mn/Mn cofactor in vitro , under both aerobic and anoxic conditions, when the metal-free protein is subjected to incubation with Mn II and Fe II in equal concentrations. This observation provides an example of a protein scaffold intrinsically predisposed to defy the Irving–Williams series and supports the assumption that the Mn/Mn cofactor is the biologically relevant cofactor in vivo. Substitution of a second coordination sphere residue changes the spontaneous metallation of the protein to predominantly form a heterodinuclear Mn/Fe cofactor under aerobic conditions and a Mn/Mn metal center under anoxic conditions. Together, the results describe the intrinsic metal specificity of class Ib RNR and provide insight into control mechanisms for protein metallation. Graphical Abstract

Photoperiodic effects on the male gonads of the Namibian gerbil, Gerbilliscus cf. leucogaster from central Namibia - Sachariah P. Muteka; Christian T. Chimimba; Armanda D. S. Bastos; Nigel C. Bennett (Mammalian Biology, 2020)

An investigation into the use of < 38 µm fraction as a proxy for < 10 µm road dust particles - Andrew D. Brown; Judith E. S. Barrett; Michael Bennett; Sanja Potgieter-Vermaak (Environmental Geochemistry and Health, 2020)

Seeds of good anthropocenes: developing sustainability scenarios for Northern Europe - C. Raudsepp-Hearne; G. D. Peterson; E. M. Bennett; R. Biggs; A. V. Norström; L. Pereira; J. Vervoort; D. M. Iwaniec; T. McPhearson; P. Olsson; T. Hichert; M. Falardeau; et al. (Sustainability Science, 2020)

Status and trends in Arctic vegetation: Evidence from experimental warming and long-term monitoring - Anne D. Bjorkman; Mariana García Criado; Isla H. Myers-Smith; Virve Ravolainen; Ingibjörg Svala Jónsdóttir; Kristine Bakke Westergaard; James P. Lawler; Mora Aronsson; Bruce Bennett; Hans Gardfjell; Starri Heiðmarsson; Laerke Stewart; et al. (Ambio, 2020)

Medial temporal lobe volumes in late-life depression: effects of age and vascular risk factors - Warren D. Taylor; Yi Deng; Brian D. Boyd; Manus J. Donahue; Kimberly Albert; Maureen McHugo; Jason A Gandelman; Bennett A. Landman (Brain Imaging and Behavior, 2020)

Morphological and molecular characterisation of a new genus and species of acanthocephalan, Tenuisoma tarapungi n. g., n. sp. (Acanthocephala: Polymorphidae) infecting red-billed gulls in New Zealand, with a key to the genera of the Polymorphidae Meyer, 1931 - Bronwen Presswell; Jerusha D. L. Bennett; Lesley R. Smales (Systematic Parasitology, 2020)

Relative costs of conserving threatened species across taxonomic groups - Elizabeth Robson Gordon; Nathalie Butt; Hanna Rosner‐Katz; Allison D. Binley; Joseph R. Bennett (Conservation Biology, 2020)
Bias toward legally protecting and prioritizing charismatic taxonomic groups, such as mammals and birds, and against others, such as insects and plants, is well documented. However, the relative costs of conserving various taxonomic groups and the potential of these costs to interact with existing biases have been much less explored. We analyzed conservation programs across more than 2,000 species in 3 countries to investigate the costs of conserving species within taxonomic groups and how these costs might affect conservation planning. For each data set, we tested for differences in mean annual cost among taxonomic groups. For the data set from the United States, recovery plans differed in duration, so we also tested for differences in total costs among taxonomic groups. Although the costs for individual species varied widely, there were strong international consistencies. For example, mammals cost 8–26 times more on average to conserve than plants and 13–19 times more to conserve than aquatic invertebrates. On average, bird species cost 5–30 times more to conserve than plants and 6–14 times more to conserve than aquatic invertebrates. These cost differences could exacerbate unequal resource allocation among taxonomic groups such that more charismatic groups both receive more attention and require more resources, leading to neglect of other taxonomic groups.

Wildfire refugia in forests: Severe fire weather and drought mute the influence of topography and fuel age - Luke Collins; Andrew F. Bennett; Steve W. J. Leonard; Trent D. Penman (Global Change Biology, 2019)
Wildfire refugia (unburnt patches within large wildfires) are important for the persistence of fire‐sensitive species across forested landscapes globally. A key challenge is to identify the factors that determine the distribution of fire refugia across space and time. In particular, determining the relative influence of climatic and landscape factors is important in order to understand likely changes in the distribution of wildfire refugia under future climates. Here, we examine the relative effect of weather (i.e. fire weather, drought severity) and landscape features (i.e. topography, fuel age, vegetation type) on the occurrence of fire refugia across 26 large wildfires in south‐eastern Australia. Fire weather and drought severity were the primary drivers of the occurrence of fire refugia, moderating the effect of landscape attributes. Unburnt patches rarely occurred under ‘severe’ fire weather, irrespective of drought severity, topography, fuels or vegetation community. The influence of drought severity and landscape factors played out most strongly under ‘moderate’ fire weather. In mesic forests, fire refugia were linked to variables that affect fuel moisture, whereby the occurrence of unburnt patches decreased with increasing drought conditions and were associated with more mesic topographic locations (i.e. gullies, pole‐facing aspects) and vegetation communities (i.e. closed‐forest). In dry forest, the occurrence of refugia was responsive to fuel age, being associated with recently burnt areas (

Redox-induced structural changes in the di-iron and di-manganese forms of Bacillus anthracis ribonucleotide reductase subunit NrdF suggest a mechanism for gating of radical access - Kristīne Grāve; Wietske Lambert; Gustav Berggren; Julia J. Griese; Matthew D. Bennett; Derek T. Logan; Martin Högbom (JBIC Journal of Biological Inorganic Chemistry, 2019)

The provision and utility of earth science to decision-makers: synthesis and key findings - Mark C. Quigley; Luke G. Bennetts; Patricia Durance; Petra M. Kuhnert; Mark D. Lindsay; Keith G. Pembleton; Melanie E. Roberts; Christopher J. White (Environment Systems and Decisions, 2019)

The provision and utility of science and uncertainty to decision-makers: earth science case studies - Mark C. Quigley; Luke G. Bennetts; Patricia Durance; Petra M. Kuhnert; Mark D. Lindsay; Keith G. Pembleton; Melanie E. Roberts; Christopher J. White (Environment Systems and Decisions, 2019)

Gene expression and DNA methylation are extensively coordinated with MRI-based brain microstructural characteristics - Chris Gaiteri; Robert Dawe; Sara Mostafavi; Katherine D. Blizinsky; Shinya Tasaki; Vitalina Komashko; Lei Yu; Yanling Wang; Julie A. Schneider; Konstantinos Arfanakis; Philip L. De Jager; David A. Bennett (Brain Imaging and Behavior, 2019)

Sex Differences in Gene and Protein Expression After Intracerebral Hemorrhage in Mice - Yongqiu Xie; Yi-Ju Li; Beilei Lei; Dawn Kernagis; Wen-Wei Liu; Ellen R. Bennett; Talagnair Venkatraman; Christopher D. Lascola; Daniel T. Laskowitz; David S. Warner; Michael L. James (Translational Stroke Research, 2019)

Prevalence of BFDV in wild breeding Platycercus elegans - Justin R. Eastwood; Mathew L. Berg; Raoul F. H. Ribot; Katherine L. Buchanan; Ken Walder; Andrew T. D. Bennett (Journal of Ornithology, 2019)

Plumage coloration follows Gloger's rule in a ring species - Raoul F. H. Ribot; Mathew L. Berg; Emanuel Schubert; John A. Endler; Andrew T. D. Bennett (Journal of Biogeography, 2019)
Aim Animal coloration is expected to differ between populations in different habitats according to Gloger's rule, with darker animals found in more humid, vegetated or warmer environments. Yet despite considerable support across the globe, the mechanisms behind this biogeographical rule are currently still unclear. Exploiting a ring species with plumage coloration from crimson to pale yellow, we test Gloger's rule and the mechanisms behind phenotypic divergence. Location South‐eastern Australia. Major taxa studied Crimson rosellas ( Platycercus elegans ). Methods We combined three modelling approaches (spatial regression; random decision forest species distribution and conditional inference tree) to test the association between 10 environmental variables (based on long‐term climate data and remotely sensed reflectance of the land) and plumage coloration across the distribution of P. elegans . We also took in‐situ measurements of background coloration of dominant vegetation to examine the relationship between (a) background coloration measured locally and remotely, (b) P. elegans coloration and (c) known differences in visual sensitivity of the subspecies using species‐specific visual models. Results On both a continental and a local scale, the distribution of yellow‐red plumage coloration was strongly predicted by average rainfall, summer temperature and the Earth's reflectance between 620–670 nm. Remotely sensed radiance measures correlated strongly and positively with reflectance of the leaves of the dominant tree species at sites across the P. elegans distribution. Visual modelling indicated that differences in background colour could affect signalling efficacy in dim‐light conditions. Main conclusions Our study shows that the highly variable plumage coloration conforms to Gloger's rule, and indicates that background coloration of the vegetation and thermoregulation are likely to be important mechanisms. Our results also show that Gloger's rule can explain variation in pigmentary systems other than melanin, and highlight that selection from environmental variation could be an important force behind the geographic diversity found in ring species.

Movement and predation: a catch-and-release study on the acoustic tracking of bonefish in the Indian Ocean - Emily J. Moxham; Paul D. Cowley; Rhett H. Bennett; Rainer G. von Brandis (Environmental Biology of Fishes, 2019)

Rare loss of function variants in candidate genes and risk of colorectal cancer - Elisabeth A. Rosenthal; Brian H. Shirts; Laura M. Amendola; Martha Horike-Pyne; Peggy D. Robertson; Fuki M. Hisama; Robin L. Bennett; Michael O. Dorschner; Deborah A. Nickerson; Ian B. Stanaway; Rami Nassir; Kathy T. Vickers; et al. (Human Genetics, 2018)

Research Priorities to Support Effective Manta and Devil Ray Conservation - Joshua D. Stewart; Fabrice R. A. Jaine; Amelia J. Armstrong; Asia O. Armstrong; Michael B. Bennett; Katherine B. Burgess; Lydie I. E. Couturier; Donald A. Croll; Melissa R. Cronin; Mark H. Deakos; Christine L. Dudgeon; Daniel Fernando; et al. (Frontiers in Marine Science, 2018)

What are the Conditions of Riparian Ecosystems? Identifying Impaired Floodplain Ecosystems across the Western U.S. Using the Riparian Condition Assessment (RCA) Tool - William W. Macfarlane; Jordan T. Gilbert; Joshua D. Gilbert; William C. Saunders; Nate Hough-Snee; Chalese Hafen; Joseph M. Wheaton; Stephen N. Bennett (Environmental Management, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Neutron and X-ray total scattering study of hydrogen disorder in fully hydrated hydrogrossular, Ca3Al2(O4H4)3 - David A. Keen; Dean S. Keeble; Thomas D. Bennett (Physics and Chemistry of Minerals, 2018)

Equity trade‐offs in conservation decision making - Elizabeth A. Law; Nathan J. Bennett; Christopher D. Ives; Rachel Friedman; Katrina J. Davis; Carla Archibald; Kerrie A. Wilson (Conservation Biology, 2018)
Conservation decisions increasingly involve multiple environmental and social objectives, which result in complex decision contexts with high potential for trade‐offs. Improving social equity is one such objective that is often considered an enabler of successful outcomes and a virtuous ideal in itself. Despite its idealized importance in conservation policy, social equity is often highly simplified or ill‐defined and is applied uncritically. What constitutes equitable outcomes and processes is highly normative and subject to ethical deliberation. Different ethical frameworks may lead to different conceptions of equity through alternative perspectives of what is good or right. This can lead to different and potentially conflicting equity objectives in practice. We promote a more transparent, nuanced, and pluralistic conceptualization of equity in conservation decision making that particularly recognizes where multidimensional equity objectives may conflict. To help identify and mitigate ethical conflicts and avoid cases of good intentions producing bad outcomes, we encourage a more analytical incorporation of equity into conservation decision making particularly during mechanistic integration of equity objectives. We recommend that in conservation planning motivations and objectives for equity be made explicit within the problem context, methods used to incorporate equity objectives be applied with respect to stated objectives, and, should objectives dictate, evaluation of equity outcomes and adaptation of strategies be employed during policy implementation.

Causes and consequences of human induced impacts on a ubiquitous estuary-dependent marine fish species - Alan K. Whitfield; Gareth N. Grant; Rhett H. Bennett; Paul D. Cowley (Reviews in Fish Biology and Fisheries, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Morphological comparison of the ampullae of Lorenzini of three sympatric benthic rays - A. R. G. Gauthier; D. L. Whitehead; I. R. Tibbetts; B. W. Cribb; M. B. Bennett (Journal of Fish Biology, 2018)
This study investigated and compared the morphology of the electrosensory system of three species of benthic rays . Neotrygon trigonoides , Hemitrygon fluviorum and Maculabatis toshi inhabit similar habitats within Moreton Bay, Queensland, Australia. Like all elasmobranchs, they possess the ability to detect weak electrical fields using their ampullae of Lorenzini. Macroscopically, the ampullary organs of all three species are aggregated in three bilaterally paired clusters: the mandibular, hyoid and superficial ophthalmic clusters. The hyoid and superficial ophthalmic clusters of ampullae arise from both dorsal and ventral ampullary pores. The dorsal pores are typically larger than the ventral pores in all three species, except for the posterior ventral pores of the hyoid grouping. Ampullary canals arising from the hyoid cluster possessed a quasi‐sinusoidal shape, but otherwise appeared similar to the canals described for other elasmobranchs. Ultrastructure of the ampullae of Lorenzini of the three species was studied using a combination of light, confocal and electron microscopy. All possess ampullae of the alveolar type. In N. trigonoides and M. toshi, each ampullary canal terminates in three to five sensory chambers, each comprising several alveoli lined with receptor and supportive cells and eight to 11 sensory chambers in H. fluviorum . Receptor cells of all three species possess a similar organization to those of other elasmobranchs and were enveloped by large, apically nucleated supportive cells protruding well into the alveolar sacs. The luminally extended chassis of supportive cells protruding dramatically into the ampullary lumen had not previously been documented for any elasmobranch species.

Long‐distance flights and high‐risk breeding by nomadic waterbirds on desert salt lakes - Reece D. Pedler; Raoul F.H. Ribot; Andrew T.D. Bennett (Conservation Biology, 2018)
Understanding and conserving mobile species presents complex challenges, especially for animals in stochastic or changing environments. Nomadic waterbirds must locate temporary water in arid biomes where rainfall is highly unpredictable in space and time. To achieve this they need to travel over vast spatial scales and time arrival to exploit pulses in food resources. How they achieve this is an enduring mystery. We investigated these challenges in the colonial‐nesting Banded Stilt ( Cladorhynchus leucocephalus ), a nomadic shorebird of conservation concern. Hitherto, Banded Stilts were hypothesized to have only 1–2 chances to breed during their long lifetime, when flooding rain fills desert salt lakes, triggering mass‐hatching of brine shrimp. Over 6 years, we satellite tagged 57 individuals, conducted 21 aerial surveys to detect nesting colonies on 14 Australian desert salt lakes, and analyzed 3 decades of Landsat and MODIS satellite imagery to quantify salt‐lake flood frequency and extent. Within days of distant inland rainfall, Banded Stilts flew 1,000–2,000 km to reach flooded salt lakes. On arrival, females laid over half their body weight in eggs. We detected nesting episodes across the species’ range at 7 times the frequency reported during the previous 80 years. Nesting colonies of thousands formed following minor floods, yet most were subsequently abandoned when the water rapidly evaporated prior to egg hatching. Satellite imagery revealed twice as many flood events sufficient for breeding‐colony initiation as recorded colonies, suggesting that nesting at remote sites has been underdetected. Individuals took risk on uncertain breeding opportunities by responding to frequent minor flood events between infrequent extensive flooding, exemplifying the extreme adaptability and trade‐offs of species exploiting unstable environments. The conservation challenges of nest predation by overabundant native gulls and anthropogenic modifications to salt lakes filling frequencies require investigation, as do the physiological and navigational mechanisms that enable such extreme strategies.

Effects of cholesterol, C-reactive protein, and interleukin-6 on prostate cancer risk in a population of African ancestry - Marshall K. Tulloch-Reid; Norma McFarlane-Anderson; Franklyn I. Bennett; William D. Aiken; Maria D. Jackson (Cancer Causes & Control, 2017)

Influences of selected geophysical and environmental drivers on the movement patterns of Rhabdosargus holubi in a southern African estuary - Gareth N. Grant; Paul D. Cowley; Rhett H. Bennett; Amber-Robyn Childs; Alan K. Whitfield (Environmental Biology of Fishes, 2017)

Trace metal content in inhalable particulate matter (PM2.5–10 and PM2.5) collected from historical mine waste deposits using a laboratory-based approach - Rachael Martin; Kim Dowling; Dora C. Pearce; Singarayer Florentine; Stafford McKnight; Eduard Stelcer; David D. Cohen; Attila Stopic; John W. Bennett (Environmental Geochemistry and Health, 2017)

Balancing generality and specificity in ecological gradient analysis with species abundance distributions and individual size distributions - Jian D. L. Yen; James R. Thomson; Jonathan M. Keith; David M. Paganin; Erica Fleishman; David S. Dobkin; Joanne M. Bennett; Ralph Mac Nally (Global Ecology and Biogeography, 2017)
Aim Data on ecological communities are often condensed into single‐valued diversity indices, which support comparisons among ecosystems but may discard important information. At the other extreme, some studies retain full data on the identities of all species present, which retains maximum information on community structure but occludes comparisons among ecosystems. We sought to determine whether the analysis of species abundance distributions and individual size distributions could support more detailed inferences than diversity indices while remaining sufficiently general to identify fundamental ecological responses in multiple ecosystems. Location The United States and south‐eastern Australia. Methods We analysed changes in species abundance distributions and individual size distributions along environmental gradients. We compared analyses of distributions with analyses of five diversity indices and with a distance‐based multivariate analysis of species composition. We used data from 1438 fish communities in the United States and from 840 bird communities in the western United States and south‐eastern Australia. These communities were sampled over 10–20 years and included 298 species of birds and 488 species of fishes. Results Analyses of species abundance distributions and individual size distributions identified environmental associations that were not found in analyses of diversity indices, and revealed common associations with shrubs in bird communities on different continents and with temperature in communities of birds and fishes. Individual size distributions were associated more closely with environmental variables than were species abundance distributions. Main conclusions Our novel identification of ecological associations suggests that analyses of community distributions might reveal fundamental ecological processes common to multiple ecosystems. Close associations between individual sizes and environmental variables suggest that a greater focus on size in ecological analyses might assist in the development of general models of ecological communities.

Can estimates of genetic effective population size contribute to fisheries stock assessments? - J. R. Ovenden; G. M. Leigh; D. C. Blower; A. T. Jones; A. Moore; C. Bustamante; R. C. Buckworth; M. B. Bennett; C. L. Dudgeon (Journal of Fish Biology, 2016)
Sustainable exploitation of fisheries populations is challenging to achieve when the size of the population prior to exploitation and the actual numbers removed over time and across fishing zones are not clearly known. Quantitative fisheries' modeling is able to address this problem, but accurate and reliable model outcomes depend on high quality input data. Much of this information is obtained through the operation of the fishery under consideration, but while this seems appropriate, biases may occur. For example, poorly quantified changes in fishing methods that increase catch rates can erroneously suggest that the overall population size is increasing. Hence, the incorporation of estimates of abundance derived from independent data sources is preferable. We review and evaluate a fisheries‐independent method of indexing population size; inferring adult abundance from estimates of the genetic effective size of a population ( N e ). Recent studies of elasmobranch species have shown correspondence between N e and ecologically determined estimates of the population size ( N ). Simulation studies have flagged the possibility that the range of N e / N ratios across species may be more restricted than previously thought, and also show that declines in N e track declines in the abundance of model fisheries species. These key developments bring this new technology closer to implementation in fisheries science, particularly for data‐poor fisheries or species of conservation interest.

Evidence for extensive but variable nutrient limitation in New Zealand lakes - Amy C. Krist; Adam D. Kay; Elizabeth Scherber; Katelyn Larkin; Bennett J. Brown; Diana Lu; Donald T. Warren; Ruth Riedl; Maurine Neiman (Evolutionary Ecology, 2016)

The effect of age and microstructural white matter integrity on lap time variation and fast-paced walking speed - Qu Tian; Luigi Ferrucci; Susan M. Resnick; Eleanor M. Simonsick; Michelle D. Shardell; Bennett A. Landman; Vijay K. Venkatraman; Christopher E. Gonzalez; Stephanie A. Studenski (Brain Imaging and Behavior, 2016)

Design and Verification of Novel Low-Cost MR-Guided Small-Animal Stereotactic System - Jonathan D. Plasencia; Leland S. Hu; Gregory H. Turner; Kevin M. Bennett; David H. Frakes (Journal of Medical and Biological Engineering, 2016)

Community assembly on isolated islands: macroecology meets evolution - A. J. Rominger; K. R. Goodman; J. Y. Lim; E. E. Armstrong; L. E. Becking; G. M Bennett; M. S. Brewer; D. D. Cotoras; C. P. Ewing; J. Harte; N. D. Martinez; P. M. O'Grady; et al. (Global Ecology and Biogeography, 2016)
Aim Understanding how ecological and evolutionary processes together determine patterns of biodiversity remains a central aim in biology. Guided by ecological theory, we use data from multiple arthropod lineages across the Hawaiian archipelago to explore the interplay between ecological (population dynamics, dispersal, trophic interactions) and evolutionary (genetic structuring, adaptation, speciation, extinction) processes. Our goal is to show how communities develop from the dynamic feedbacks that operate at different temporal and spatial scales. Location The Hawaiian islands (19–22° N , 155–160° W ). Methods We synthesize genetic data from selected arthropods across the Hawaiian archipelago to determine the relative role of dispersal and in situ differentiation across the island chronosequence. From four sites on three high islands with geological ages ranging from Results From the perspective of the island chronosequence we show that species at lower trophic levels develop population genetic structure at smaller temporal and spatial scales than species at higher trophic levels. Network nestedness decreases while modularity increases with habitat age. Single‐island endemics exhibit more specialization than broadly distributed species, but both show the least specialization in communities on middle‐aged substrates. Plant–herbivore networks also show the least deviation from theoretical predictions in middle‐aged communities. Main conclusions The application of ecological theory to island chronosequences can illuminate feedbacks between ecological and evolutionary processes in community assembly. We show how patterns of population genetic structure, decreasing network nestedness, increasing network modularity and increased specialization shift from early assembly driven by immigration, to in situ diversification after > 1 Myr. Herbivore–plant communities only transiently achieve statistical steady state during assembly, presumably due to incomplete assembly from dispersal in the early stages, and the increasing influence of island ontogeny on older islands.

Grey matter correlates of susceptibility to scams in community-dwelling older adults - S. Duke Han; Patricia A. Boyle; Lei Yu; Konstantinos Arfanakis; Bryan D. James; Debra A. Fleischman; David A. Bennett (Brain Imaging and Behavior, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Continental‐scale variation in seaweed host‐associated bacterial communities is a function of host condition, not geography - Ezequiel M. Marzinelli; Alexandra H. Campbell; Enrique Zozaya Valdes; Adriana Vergés; Shaun Nielsen; Thomas Wernberg; Thibaut de Bettignies; Scott Bennett; J. Gregory Caporaso; Torsten Thomas; Peter D. Steinberg (Environmental Microbiology, 2015)
Summary Interactions between hosts and associated microbial communities can fundamentally shape the development and ecology of ‘holobionts’, from humans to marine habitat‐forming organisms such as seaweeds. In marine systems, planktonic microbial community structure is mainly driven by geography and related environmental factors, but the large‐scale drivers of host‐associated microbial communities are largely unknown. Using 16S‐r RNA gene sequencing, we characterized 260 seaweed‐associated bacterial and archaeal communities on the kelp E cklonia radiata from three biogeographical provinces spanning 10° of latitude and 35° of longitude across the Australian continent. These phylogenetically and taxonomically diverse communities were more strongly and consistently associated with host condition than geographical location or environmental variables, and a ‘core’ microbial community characteristic of healthy kelps appears to be lost when hosts become stressed. Microbial communities on stressed individuals were more similar to each other among locations than those on healthy hosts. In contrast to biogeographical patterns of planktonic marine microbial communities, host traits emerge as critical determinants of associated microbial community structure of these holobionts, even at a continental scale.

Assessment of toxicity and coagulopathy of brodifacoum in Japanese quail and testing in wild owls - Kirstin H. Webster; Kendal E. Harr; Darin C. Bennett; Tony D. Williams; Kimberly M. Cheng; France Maisonneuve; John E. Elliott (Ecotoxicology, 2015)

Conformational dynamics of metallo-β-lactamase CcrA during catalysis investigated by using DEER spectroscopy - Mahesh Aitha; Lindsay Moritz; Indra D. Sahu; Omar Sanyurah; Zahilyn Roche; Robert McCarrick; Gary A. Lorigan; Brian Bennett; Michael W. Crowder (JBIC Journal of Biological Inorganic Chemistry, 2015)

Ecology of the invasive New Zealand mud snail, Potamopyrgus antipodarum (Hydrobiidae), in a mediterranean-climate stream system - Danuta M. Bennett; Tom L. Dudley; Scott D. Cooper; Samuel S. Sweet (Hydrobiologia, 2015)

Impact of fresh root material and mature crop residues of oilseed rape (Brassica napus) on microbial communities associated with subsequent oilseed rape - Amanda J. Bennett; Sally Hilton; Gary D. Bending; David Chandler; Peter Mills (Biology and Fertility of Soils, 2014)

The potential for indirect effects between co‐flowering plants via shared pollinators depends on resource abundance, accessibility and relatedness - Luísa Gigante Carvalheiro; Jacobus Christiaan Biesmeijer; Gita Benadi; Jochen Fründ; Martina Stang; Ignasi Bartomeus; Christopher N. Kaiser‐Bunbury; Mathilde Baude; Sofia I. F. Gomes; Vincent Merckx; Katherine C. R. Baldock; Andrew T. D. Bennett; et al. (Ecology Letters, 2014)
Co‐flowering plant species commonly share flower visitors, and thus have the potential to influence each other's pollination. In this study we analysed 750 quantitative plant–pollinator networks from 28 studies representing diverse biomes worldwide. We show that the potential for one plant species to influence another indirectly via shared pollinators was greater for plants whose resources were more abundant (higher floral unit number and nectar sugar content) and more accessible. The potential indirect influence was also stronger between phylogenetically closer plant species and was independent of plant geographic origin (native vs. non‐native). The positive effect of nectar sugar content and phylogenetic proximity was much more accentuated for bees than for other groups. Consequently, the impact of these factors depends on the pollination mode of plants, e.g. bee or fly pollinated. Our findings may help predict which plant species have the greatest importance in the functioning of plant–pollination networks.

Validating DICOM Transcoding with an Open Multi-Format Resource - Benjamin C. Yvernault; Charles D. Theobald; Jolinda C. Smith; Victoria Villalta; David H. Zald; Bennett A. Landman (Neuroinformatics, 2014)

The roles of oxygen and ammonia in the symbiotic relationship between the spotted salamander Ambystoma maculatum and the green alga Oophila amblystomatis during embryonic development - Daniel P. Small; R. Scott Bennett; Cory D. Bishop (Symbiosis, 2014)

Anthropogenic‐based regional‐scale factors most consistently explain plot‐level exotic diversity in grasslands - Andrew S. MacDougall; Joseph R. Bennett; Jennifer Firn; Eric W. Seabloom; Elizabeth T. Borer; Eric M. Lind; John L. Orrock; W. Stanley Harpole; Yann Hautier; Peter B. Adler; Elsa Cleland; Kendi Davies; et al. (Global Ecology and Biogeography, 2014)
Aim Evidence linking the accumulation of exotic species to the suppression of native diversity is equivocal, often relying on data from studies that have used different methods. Plot‐level studies often attribute inverse relationships between native and exotic diversity to competition, but regional abiotic filters, including anthropogenic influences, can produce similar patterns. We seek to test these alternatives using identical scale‐dependent sampling protocols in multiple grasslands on two continents. Location Thirty‐two grassland sites in N orth A merica and A ustralia. Methods We use multiscale observational data, collected identically in grain and extent at each site, to test the association of local and regional factors with the plot‐level richness and abundance of native and exotic plants. Sites captured environmental and anthropogenic gradients including land‐use intensity, human population density, light and soil resources, climate and elevation. Site selection occurred independently of exotic diversity, meaning that the numbers of exotic species varied randomly thereby reducing potential biases if only highly invaded sites were chosen. Results Regional factors associated directly or indirectly with human activity had the strongest associations with plot‐level diversity. These regional drivers had divergent effects: urban‐based economic activity was associated with high exotic : native diversity ratios; climate‐ and landscape‐based indicators of lower human population density were associated with low exotic : native ratios. Negative correlations between plot‐level native and exotic diversity, a potential signature of competitive interactions, were not prevalent; this result did not change along gradients of productivity or heterogeneity. Main conclusion We show that plot‐level diversity of native and exotic plants are more consistently associated with regional‐scale factors relating to urbanization and climate suitability than measures indicative of competition. These findings clarify the long‐standing difficulty in resolving drivers of exotic diversity using single‐factor mechanisms, suggesting that multiple interacting anthropogenic‐based processes best explain the accumulation of exotic diversity in modern landscapes.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Seasonal changes in burrow geometry of the common mole rat (Rodentia: Bathyergidae) - H. G. Thomas; M. Scantlebury; D. Swanepoel; P. W. Bateman; N. C. Bennett (The Science of Nature, 2013)

A standardised protocol for the validation of banking methodologies for arterial allografts - R. J. Lomas; P. D. F. Dodd; P. Rooney; D. E. Pegg; P. A. Hogg; M. E. Eagle; K. E. Bennett; A. Clarkson; J. N. Kearney (Cell and Tissue Banking, 2013)

Ecogeographic analysis of pea collection sites from China to determine potential sites with abiotic stresses - Ling Li; Robert J. Redden; Xuxiao Zong; J. D. Berger; Sarita Jane Bennett (Genetic Resources and Crop Evolution, 2013)

Molecular‐ and pollen‐based vegetation analysis in lake sediments from central S candinavia - Laura Parducci; Irina Matetovici; Sonia L. Fontana; K. D. Bennett; Yoshihisa Suyama; James Haile; Kurt H. Kjær; Nicolaj K. Larsen; Andreas D. Drouzas; Eske Willerslev (Molecular Ecology, 2013)
Plant and animal biodiversity can be studied by obtaining DNA directly from the environment. This new approach in combination with the use of generic barcoding primers (metabarcoding) has been suggested as complementary or alternative to traditional biodiversity monitoring in ancient soil sediments. However, the extent to which metabarcoding truly reflects plant composition remains unclear, as does its power to identify species with no pollen or macrofossil evidence. Here, we compared pollen‐based and metabarcoding approaches to explore the H olocene plant composition around two lakes in central S candinavia. At one site, we also compared barcoding results with those obtained in earlier studies with species‐specific primers. The pollen analyses revealed a larger number of taxa (46), of which the majority (78%) was not identified by metabarcoding. The metabarcoding identified 14 taxa ( MTU s), but allowed identification to a lower taxonomical level. The combined analyses identified 52 taxa. The barcoding primers may favour amplification of certain taxa, as they did not detect taxa previously identified with species‐specific primers. Taphonomy and selectiveness of the primers are likely the major factors influencing these results. We conclude that metabarcoding from lake sediments provides a complementary, but not an alternative, tool to pollen analysis for investigating past flora. In the absence of other fossil evidence, metabarcoding gives a local and important signal from the vegetation, but the resulting assemblages show limited capacity to detect all taxa, regardless of their abundance around the lake. We suggest that metabarcoding is followed by pollen analysis and the use of species‐specific primers to provide the most comprehensive signal from the environment.

Novel Mutations Mapping to the Fourth Sodium Channel Domain of Nav1.7 Result in Variable Clinical Manifestations of Primary Erythromelalgia - Roman Cregg; Bisola Laguda; Robert Werdehausen; James J. Cox; John E. Linley; Juan D. Ramirez; Istvan Bodi; Michael Markiewicz; Kevin J. Howell; Ya-Chun Chen; Karen Agnew; Henry Houlden; et al. (NeuroMolecular Medicine, 2013)

Females and attention to eye gaze: effects of the menstrual cycle - Felicity D. A. Wolohan; Sarah J. V. Bennett; Trevor J. Crawford (Experimental Brain Research, 2013)

Relationships between stream phosphorus concentrations and drainage basin characteristics in a watershed with poultry farming - Timothy J. Cox; Bernard A. Engel; Roger L. Olsen; J. B. Fisher; Andrew D. Santini; Brian J. Bennett (Nutrient Cycling in Agroecosystems, 2013)

Genome-wide association mapping of blood cell traits in mice - Richard C. Davis; Atila van Nas; Brian Bennett; Luz Orozco; Calvin Pan; Christoph D. Rau; Eleazar Eskin; Aldons J. Lusis (Mammalian Genome, 2013)

Fire Mosaics and Reptile Conservation in a Fire‐Prone Region - D. G. NIMMO; L. T. KELLY; L. M. SPENCE‐BAILEY; S. J. WATSON; R. S. TAYLOR; M. F. CLARKE; A. F. BENNETT (Conservation Biology, 2013)
Fire influences the distribution of fauna in terrestrial biomes throughout the world. Use of fire to achieve a mosaic of vegetation in different stages of succession after burning (i.e., patch‐mosaic burning) is a dominant conservation practice in many regions. Despite this, knowledge of how the spatial attributes of vegetation mosaics created by fire affect fauna is extremely scarce, and it is unclear what kind of mosaic land managers should aim to achieve. We selected 28 landscapes (each 12.6 km 2 ) that varied in the spatial extent and diversity of vegetation succession after fire in a 104,000 km 2 area in the semiarid region of southeastern Australia. We surveyed for reptiles at 280 sites nested within the 28 landscapes. The landscape‐level occurrence of 9 of the 22 species modeled was associated with the spatial extent of vegetation age classes created by fire. Biogeographic context and the extent of a vegetation type influenced 7 and 4 species, respectively. No species were associated with the diversity of vegetation ages within a landscape. Negative relations between reptile occurrence and both extent of recently burned vegetation (≤10 years postfire, n = 6) and long unburned vegetation (>35 years postfire, n = 4) suggested that a coarse‐grained mosaic of areas (e.g. >1000 ha) of midsuccessional vegetation (11–35 years postfire) may support the fire‐sensitive reptile species we modeled. This age class coincides with a peak in spinifex cover, a keystone structure for reptiles in semiarid and arid Australia. Maintaining over the long term a coarse‐grained mosaic of large areas of midsuccessional vegetation in mallee ecosystems will need to be balanced against the short‐term negative effects of large fires on many reptile species and a documented preference by species from other taxonomic groups, particularly birds, for older vegetation. Mosaicos de Fuego y la Conservación de Reptiles en una Región Propensa al Fuego

Context dependence in foraging behaviour of Achillea millefolium - Justine D. Karst; Pamela R. Belter; Jonathan A. Bennett; James F. Cahill (Oecologia, 2012)

Hybrid mouse diversity panel: a panel of inbred mouse strains suitable for analysis of complex genetic traits - Anatole Ghazalpour; Christoph D. Rau; Charles R. Farber; Brian J. Bennett; Luz D. Orozco; Atila van Nas; Calvin Pan; Hooman Allayee; Simon W. Beaven; Mete Civelek; Richard C. Davis; Thomas A. Drake; et al. (Mammalian Genome, 2012)

Phosphorus regulates stream injury by filamentous green algae, DO, and pH with thresholds in responses - R. Jan Stevenson; Brian J. Bennett; Donielle N. Jordan; Ron D. French (Hydrobiologia, 2012)

TOMM40 in Cerebral Amyloid Angiopathy Related Intracerebral Hemorrhage: Comparative Genetic Analysis with Alzheimer’s Disease - Valerie Valant; Brendan T. Keenan; Christopher D. Anderson; Joshua M. Shulman; William J. Devan; Alison M. Ayres; Kristin Schwab; Joshua N. Goldstein; Anand Viswanathan; Steven M. Greenberg; David A. Bennett; Philip L. De Jager; et al. (Translational Stroke Research, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Biology, ecology and conservation of the Mobulidae - L. I. E. Couturier; A. D. Marshall; F. R. A. Jaine; T. Kashiwagi; S. J. Pierce; K. A. Townsend; S. J. Weeks; M. B. Bennett; A. J. Richardson (Journal of Fish Biology, 2012)
The Mobulidae are zooplanktivorous elasmobranchs comprising two recognized species of manta rays ( Manta spp.) and nine recognized species of devil rays ( Mobula spp.). They are found circumglobally in tropical, subtropical and temperate coastal waters. Although mobulids have been recorded for over 400 years, critical knowledge gaps still compromise the ability to assess the status of these species. On the basis of a review of 263 publications, a comparative synthesis of the biology and ecology of mobulids was conducted to examine their evolution, taxonomy, distribution, population trends, movements and aggregation, reproduction, growth and longevity, feeding, natural mortality and direct and indirect anthropogenic threats. There has been a marked increase in the number of published studies on mobulids since c . 1990, particularly for the genus Manta , although the genus Mobula remains poorly understood. Mobulid species have many common biological characteristics although their ecologies appear to be species‐specific, and sometimes region‐specific. Movement studies suggest that mobulids are highly mobile and have the potential to rapidly travel large distances. Fishing pressure is the major threat to many mobulid populations, with current levels of exploitation in target fisheries unlikely to be sustainable. Advances in the fields of population genetics, acoustic and satellite tracking, and stable‐isotope and fatty‐acid analyses will provide new insights into the biology and ecology of these species. Future research should focus on the uncertain taxonomy of mobulid species, the degree of overlap between their large‐scale movement and human activities such as fisheries and pollution, and the need for management of inter‐jurisdictional fisheries in developing nations to ensure their long‐term sustainability. Closer collaboration among researchers worldwide is necessary to ensure standardized sampling and modelling methodologies to underpin global population estimates and status.

Perils of correlating CUSUM‐transformed variables to infer ecological relationships (Breton et al. 2006; Glibert 2010) - James E. Cloern; Alan D. Jassby; Jacob Carstensen; William A. Bennett; Wim Kimmerer; Ralph Mac Nally; David H. Schoellhamer; Monika Winder (Limnology and Oceanography, 2012)

Intermolt development reduces oxygen delivery capacity and jumping performance in the American locust (Schistocerca americana) - Scott D. Kirkton; Lauren E. Hennessey; Bridget Duffy; Meghan M. Bennett; Wah-Keat Lee; Kendra J. Greenlee (Journal of Comparative Physiology B, 2012)

Associations of whole-blood fatty acids and dietary intakes with prostate cancer in Jamaica - Maria D. Jackson; Susan P. Walker; Candace M. Simpson-Smith; Carole M. Lindsay; Garret Smith; Norma McFarlane-Anderson; Franklyn I. Bennett; Kathleen C. M. Coard; William D. Aiken; Trevor Tulloch; Tomlin J. Paul; Robert L. Wan (Cancer Causes & Control, 2012)

Absorbance of retinal oil droplets of the budgerigar: sex, spatial and plumage morph-related variation - Ben Knott; James K. Bowmaker; Mathew L. Berg; Andrew T. D. Bennett (Journal of Comparative Physiology A, 2012)

The effectiveness of methicillin-resistant Staphylococcus aureus colonisation screening in asymptomatic healthcare workers in an Irish orthopaedic unit - S. P. Edmundson; K. M. Hirpara; D. Bennett (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

A freshwater cyanophage whose genome indicates close relationships to photosynthetic marine cyanomyophages - Theo W. Dreher; Nathan Brown; Connie S. Bozarth; Andrew D. Schwartz; Erin Riscoe; Cameron Thrash; Samuel E. Bennett; Shin‐Cheng Tzeng; Claudia S. Maier (Environmental Microbiology, 2011)
Summary Bacteriophage S‐CRM01 has been isolated from a freshwater strain of Synechococcus and shown to be present in the upper Klamath River valley in northern California and Oregon. The genome of this lytic T4‐like phage has a 178 563 bp circular genetic map with 297 predicted protein‐coding genes and 33 tRNA genes that represent all 20‐amino‐acid specificities. Analyses based on gene sequence and gene content indicate a close phylogenetic relationship to the ‘photosynthetic’ marine cyanomyophages infecting Synechococcus and Prochlorococcus . Such relatedness suggests that freshwater and marine phages can draw on a common gene pool. The genome can be considered as being comprised of three regions. Region 1 is populated predominantly with structural genes, recognized as such by homology to other T4‐like phages and by identification in a proteomic analysis of purified virions. Region 2 contains most of the genes with roles in replication, recombination, nucleotide metabolism and regulation of gene expression, as well as 5 of the 6 signature genes of the photosynthetic cyanomyophages ( hli03 , hsp20 , mazG , phoH and psbA ; cobS is present in Region 3). Much of Regions 1 and 2 are syntenic with marine cyanomyophage genomes, except that a segment encompassing Region 2 is inverted. Region 3 contains a high proportion (85%) of genes that are unique to S‐CRM01, as well as most of the tRNA genes. Regions 1 and 2 contain many predicted late promoters, with a combination of CTAAATA and ATAAATA core sequences. Two predicted genes that are unusual in phage genomes are homologues of cellular spoT and nusG .

Size and structure of a photographically identified population of manta rays Manta alfredi in southern Mozambique - A. D. Marshall; C. L. Dudgeon; M. B. Bennett (Marine Biology, 2011)

Maternal consumption of coffee and tea during pregnancy and risk of childhood ALL: results from an Australian case–control study - Elizabeth Milne; Jill A. Royle; Lisa C. Bennett; Nicholas H. de Klerk; Helen D. Bailey; Carol Bower; Margaret Miller; John Attia; Rodney J. Scott; Maria Kirby; Bruce K. Armstrong (Cancer Causes & Control, 2011)

The control of marine biofouling on xerogel surfaces with nanometer-scale topography - Nikhil Gunari; Lenora H. Brewer; Stephanie M. Bennett; Anastasiya Sokolova; Nadine D. Kraut; John A. Finlay; Anne E. Meyer; Gilbert C. Walker; Dean E. Wendt; Maureen E. Callow; James A. Callow; Frank V. Bright; et al. (Biofouling, 2011)

Prioritisation of novel pasture species for use in water-limited agriculture: a case study of Cullen in the Western Australian wheatbelt - R. G. Bennett; M. H. Ryan; T. D. Colmer; D. Real (Genetic Resources and Crop Evolution, 2011)

The frequency and effect of shark-inflicted bite injuries to the reef manta ray Manta alfredi - A D Marshall; M B Bennett (African Journal of Marine Science, 2010)

Urinary phytoestrogens and risk of prostate cancer in Jamaican men - Maria D. Jackson; Norma D. McFarlane-Anderson; Garfield A. Simon; Franklyn I. Bennett; Susan P. Walker (Cancer Causes & Control, 2010)

Reproductive ecology of the reef manta ray Manta alfredi in southern Mozambique - A. D. Marshall; M. B. Bennett (Journal of Fish Biology, 2010)
The application of a photographic identification methodology using the unique ventral surface markings (natural spot patterns) of an observed population in southern Mozambique enabled many aspects of the reproductive ecology of reef manta rays Manta alfredi to be examined. The region encompassing the study site was identified as a mating ground for M. alfredi based on observations of mating events and fresh mating scars on females. The distribution of these pectoral fin scars was highly biased and indicated a strong lateralized behavioural trait, with 99% of these scars occurring only on the left pectoral fin. No other elasmobranch has been reported to display behavioural lateralization. The study region also acts as a birthing ground, with individuals typically giving birth in the austral summer period after a gestation of c . 1 year. Reproductive periodicity in M. alfredi was most commonly biennial, but a few individuals were pregnant in consecutive years, confirming an annual ovulatory cycle. The production of a single pup appears to be the normal situation, although observations in the wild as well as during opportunistic dissections of individuals killed by fisheries revealed that two pups are conceived on occasion. Many aspects of the study have contributed to the limited baseline data currently available for this species and have highlighted the potential need for more conservative conservation strategies.

Branching coral as a macroalgal refuge in a marginal coral reef system - S. Bennett; A. Vergés; D. R. Bellwood (Coral Reefs, 2010)

Body size and risk of prostate cancer in Jamaican men - Maria D. Jackson; Susan P. Walker; Candace M. Simpson; Norma McFarlane-Anderson; Franklyn I. Bennett; Kathleen C. M. Coard; William D. Aiken; Trevor Tulloch; Tomlin J. Paul; Robert L. Wan (Cancer Causes & Control, 2010)

Behavioral correlations across activity, mating, exploration, aggression, and antipredator contexts in the European house cricket, Acheta domesticus - Alexander D. M. Wilson; Emily M. Whattam; Rachel Bennett; Laksanavadee Visanuvimol; Chris Lauzon; Susan M. Bertram (Behavioral Ecology and Sociobiology, 2010)

4 °C and beyond: what did this mean for biodiversity in the past? - Kathy J. Willis; Keith D. Bennett; Shonil A. Bhagwat; H. John B. Birks (Systematics and Biodiversity, 2010)

Understanding relationships among multiple ecosystem services - Elena M. Bennett; Garry D. Peterson; Line J. Gordon (Ecology Letters, 2009)
Ecology Letters (2009) 12: 1394–1404 Abstract Ecosystem management that attempts to maximize the production of one ecosystem service often results in substantial declines in the provision of other ecosystem services. For this reason, recent studies have called for increased attention to development of a theoretical understanding behind the relationships among ecosystem services. Here, we review the literature on ecosystem services and propose a typology of relationships between ecosystem services based on the role of drivers and the interactions between services. We use this typology to develop three propositions to help drive ecological science towards a better understanding of the relationships among multiple ecosystem services. Research which aims to understand the relationships among multiple ecosystem services and the mechanisms behind these relationships will improve our ability to sustainably manage landscapes to provide multiple ecosystem services.

The role of surface energy and water wettability in aminoalkyl/fluorocarbon/hydrocarbon-modified xerogel surfaces in the control of marine biofouling - Stephanie M. Bennett; John A. Finlay; Nikhil Gunari; David D. Wells; Anne E. Meyer; Gilbert C. Walker; Maureen E. Callow; James A. Callow; Frank V. Bright; Michael R. Detty (Biofouling, 2009)

Composition and location of simulated lake‐shore redds influence incubation success in kokanee, Oncorhynchus nerka - M. J. FINCEL; S. R. CHIPPS; D. H. BENNETT (Fisheries Management and Ecology, 2009)
Methods for improving spawning habitat for lakeshore spawning kokanee, Oncorhynchus nerka (Walbaum), were explored by quantifying incubation success of embryos exposed to three substrate treatments in Lake Pend Oreille, Idaho, USA. Substrate treatments included no modification that used existing gravels in the lake (EXISTING), a cleaned substrate treatment where existing gravels were sifted in the water column to remove silt (CLEANED) and the addition of new, silt‐free gravel (ADDED). Incubation success was evaluated using Whitlock–Vibert incubation boxes buried within each substrate treatment that contained recently fertilised embryos. Upon retrieval, live and dead sac fry and eyed eggs were enumerated to determine incubation success (sac fry and eyed eggs × 100/number of fertilised embryos). Incubation success varied significantly among locations and redd treatments. In general, incubation success among ADDED redds (0.0–13.0%) was significantly lower than that for EXISTING (1.4–61.0%) and CLEANED (0.4–62.5%) redds. Adding new gravel to spawning areas changed the morphometry of the gravel‐water interface and probably exposed embryos to disturbance from wave action and reduced embryo survival. Moreover, efforts to improve spawning habitat for lakeshore spawning kokanee should consider water depth and location (e.g. protected shorelines) as important variables. Adding clean gravel to existing spawning areas may provide little benefit if water depth or lake‐bottom morphometry are altered.

South Australian rainfall variability and climate extremes - Alexander D. Evans; John M. Bennett; Caecilia M. Ewenz (Climate Dynamics, 2009)

Variability in thermal and UV‐B energy fluxes through time and their influence on plant diversity and speciation - K. J. Willis; K. D. Bennett; H. J. B. Birks (Journal of Biogeography, 2009)
Throughout Earth’s history there have been temporal and spatial variations in the amount of visible and ultraviolet radiation received by ecosystems. This paper examines if temporal changes in these forms of energy receipt could have influenced the tempo and mode of plant diversity and speciation, focusing in particular upon Cenozoic time‐scales. Evidence for changing patterns of plant diversity and speciation apparent in various fossil records and molecular phylogenies are considered alongside calculated changes in thermal and solar ultraviolet energy (specifically UV‐B) over the past 50 Myr. We suggest that changes in thermal energy influx (amount and variability) affected the tempo of evolution through its influence upon community dynamics (e.g. population size, diversity, turnover, extinctions). It was not only the amount of thermal energy but also variability in its flux that may have influenced these processes, and ultimately the rate of diversification. We suggest that variations in UV‐B would have influenced the mode and tempo of speciation through changes to genome stability during intervals of elevated UV‐B. We argue, therefore, that although variability in thermal energy and UV‐B fluxes through time may lead to the same end‐point (changing the rate of diversification), the processes responsible are very different and both need to be considered when linking evolutionary processes to energy flux.

Angular momentum synergies during walking - Thomas Robert; Bradford C. Bennett; Shawn D. Russell; Christopher A. Zirker; Mark F. Abel (Experimental Brain Research, 2009)

Arbuscular mycorrhizal fungal species suppress inducible plant responses and alter defensive strategies following herbivory - Alison Elizabeth Bennett; James D. Bever; M. Deane Bowers (Oecologia, 2009)

Trade-offs between arbuscular mycorrhizal fungal competitive ability and host growth promotion in Plantago lanceolata - Alison Elizabeth Bennett; James D. Bever (Oecologia, 2009)

Cigarette smoking, body mass index, gastro-esophageal reflux disease, and non-steroidal anti-inflammatory drug use and risk of subtypes of esophageal and gastric cancers by P53 overexpression - Jonine D. Figueroa; Mary Beth Terry; Marilie D. Gammon; Thomas L. Vaughan; Harvey A. Risch; Fang-Fang Zhang; David E. Kleiner; William P. Bennett; Christine L. Howe; Robert Dubrow; Susan T. Mayne; Joseph F. Fraumeni; et al. (Cancer Causes & Control, 2009)

Chinese herbal medicine for Mild Cognitive Impairment and Age Associated Memory Impairment: a review of randomised controlled trials - Brian H. May; Angela W. H. Yang; Anthony L. Zhang; Michael D. Owens; Louise Bennett; Richard Head; Lynne Cobiac; Chun Guang Li; Helmut Hugel; David F. Story; Charlie C. L. Xue (Biogerontology, 2009)

Spread of an introduced vector‐borne banana virus in Hawaii - RODRIGO P.P. ALMEIDA; GORDON M. BENNETT; MANDY D. ANHALT; CHI‐WEI TSAI; PATRICK O’GRADY (Molecular Ecology, 2009)
Emerging diseases are increasing in incidence; therefore, understanding how pathogens are introduced into new regions and cause epidemics is of importance for the development of strategies that may hinder their spread. We used molecular data to study how a vector‐borne banana virus, Banana bunchy top virus (BBTV), spread in Hawaii after it was first detected in 1989. Our analyses suggest that BBTV was introduced once into Hawaii, on the island of Oahu. All other islands were infected with isolates originating from Oahu, suggesting that movement of contaminated plant material was the main driving factor responsible for interisland spread of BBTV. The rate of mutation inferred by the phylogenetic analysis (1.4 × 10 −4 bp/year) was similar to that obtained in an experimental evolution study under greenhouse conditions (3.9 × 10 −4 bp/year). We used these values to estimate the number of infections occurring under field conditions per year. Our results suggest that strict and enforced regulations limiting the movement of banana plant material among Hawaiian islands could have reduced interisland spread of this pathogen.

Comparing the diet of two sympatric urolophid elasmobranchs ( Trygonoptera testacea Müller & Henle and Urolophus kapalensis Yearsley & Last): evidence of ontogenetic shifts and possible resource partitioning - A. D. Marshall; P. M. Kyne; M. B. Bennett (Journal of Fish Biology, 2008)
The diets of two urolophids, the common stingaree Trygonoptera testacea and the kapala stingaree Urolophus kapalensis were analysed and compared to examine resource partitioning between these two morphologically similar sympatric Australian batoids. The diet of T. testacea was polychaete‐based, while that of U. kapalensis was dominated by crustaceans (mostly carid shrimps and amphipods). Intraspecific dietary compositions were examined amongst size classes within each of the two species to identify ontogenetic shifts in diet. Differences in the dietary compositions of the smaller total‐length classes of T. testacea suggest that their diet shifts as they increase in size, from one dominated by carids to one almost entirely comprising polychaetes. Significant ontogenetic dietary shifts were not identified in U. kapalensis . Although the two species shared eight broad dietary categories, their overall dietary compositions were found to be significantly different. The limited overlap in the dietary compositions of these two sympatric stingarees suggests the possibility of resource partitioning, with interspecific competition being implicated as a possible cue. Possible mechanisms for the partitioning of resources within and between these two species are discussed.

Seawater-like trace element signatures (REE + Y) of Eoarchaean chemical sedimentary rocks from southern West Greenland, and their corruption during high-grade metamorphism - C. R. L. Friend; A. P. Nutman; V. C. Bennett; M. D. Norman (Contributions to Mineralogy and Petrology, 2008)

Evaluating climatic and non-climatic influences on ion chemistry in natural and man-made lakes of Nebraska, USA - D. M. Bennett; S. C. Fritz; J. C. Holz; A. A. Holz; V. A. Zlotnik (Hydrobiologia, 2007)

The role of platelet CD154 in the modulation in adaptive immunity - Daniel L. Sprague; Jennifer M. Sowa; Bennett D. Elzey; Timothy L. Ratliff (Immunologic Research, 2007)

Continuous measurement of oxygen tensions in the air-breathing organ of Pacific tarpon (Megalops cyprinoides) in relation to aquatic hypoxia and exercise - Roger S. Seymour; Anthony P. Farrell; Keith Christian; Timothy D. Clark; Michael B. Bennett; Rufus M. G. Wells; John Baldwin (Journal of Comparative Physiology B, 2007)

Host intra-clutch variation, cuckoo egg matching and egg rejection by great reed warblers - Michael I. Cherry; Andrew T. D. Bennett; Csaba Moskát (The Science of Nature, 2007)

HIV protease inhibitors modulate apoptosis signaling in vitro and in vivo - Stacey R. Vlahakis; Steffany A. L. Bennett; Shawn N. Whitehead; Andrew D. Badley (Apoptosis, 2007)

Altered gill morphology in benthic macroinvertebrates from mercury enriched streams in the Neversink Reservoir Watershed, New York - Kathleen M. Skinner; Jessica D. Bennett (Ecotoxicology, 2007)

The Arabidopsis thaliana/Myzus persicae model system demonstrates that a single gene can influence the interaction between a plant and a sap‐feeding insect - E. J. HUNT; J. PRITCHARD; M. J. BENNETT; X. ZHU; D. A. BARRETT; T. ALLEN; JS BALE; H. J. NEWBURY (Molecular Ecology, 2006)
We have developed an Arabidopsis thaliana / Myzus persicae model system to allow the dissection of plant/insect interactions at a molecular genetic level. This allows the examination of the role of single plant genes in the interaction between the plant and an aphid. Our initial studies have exploited an Arabidopsis genotype in which the function of the amino acid transporter ANT1 has been abolished. This mutation results in a change in the proportions of several amino acids within the phloem sieve elements (SEs) resulting in an increase in the proportion of essential amino acids. This has been measured using aphid stylectomy to collect SE samples, followed by a novel micellar electrokinetic chromatography method for amino acid analysis. The SE content represents the aphid's diet, and use of electrical penetration graph technology and honeydew clocks have demonstrated that this altered diet results in a change in the feeding rate of the aphid. Balance sheets can be produced to show the amount (nmoles/24 h) of each of 18 amino acids taken up and excreted by aphids feeding on wild type and ant1 mutant plants. The data show that aphids feeding on the ant1 mutant take up larger amounts of amino acids. However, we could not detect any effect on the reproductive rate of the aphids. The results show that, under experimental conditions, this model system can be used to identify plant genes that control the behaviour and fecundity of an insect pest.

A Systems Model Approach to Determining Resilience Surrogates for Case Studies - E. M. Bennett; G. S. Cumming; G. D. Peterson (Ecosystems, 2005)

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

Ancient DNA from pollen: a genetic record of population history in Scots pine - L. PARDUCCI; Y. SUYAMA; M. LASCOUX; K. D. BENNETT (Molecular Ecology, 2005)
Assessments of plant population dynamics in space and time have depended on dated records of fossil pollen synthesized on a subcontinental scale. Genetic analyses of extant populations have revealed spatial relationships that are indicative of past spatial dynamics, but lack an explicit timescale. Synthesis of these data requires genetic analyses from abundant dated fossil material, and this has hitherto been lacking. Fossil pollen is the most abundant material with which to fill this data gap. Here we report genetic analyses of fossil pollen retrieved from Holtjärnen postglacial lake sediment in Sweden and show that plastid DNA is recoverable from Scots Pine and Norway spruce pollen grains that are 100 and 10 000 years old. By sequencing clones from two short plastid PCR products and by using multiple controls we show that the ancient sequences were endogenous to the fossil grains. Comparison of ancient sequences and those obtained from an extant population of Scots pine establishes the first genetic link between extant and fossil samples in this species, providing genetic continuity through time. The finding of one common haplotype present in modern, 100‐year old and 10 000‐year old samples suggests that it may have persisted near Holtjärnen throughout the postglacial period. This retrieval of ancient DNA from pollen has major implications for plant palaeoecology in conifer species by allowing direct estimates of population dynamics in space and time.

Rethinking Environmental Performance from a Public Health Perspective: A Comparative Industry Analysis - Dinah A. Koehler; Deborah H. Bennett; Gregory A. Norris; John D. Spengler (Journal of Industrial Ecology, 2005)
Summary To date the most common measures of environmental performance used to compare industries, and by extension firms or facilities, have been quantity of pollution emitted or hazardous waste generated. Discharge information, however, does not necessarily capture potential health effects. We propose an alternative environmental performance measure that includes the public health risks of toxic air emissions extended to industry supply chains using economic input‐output life‐cycle assessment. Cancer risk to the U.S. population was determined by applying a damage function to the Toxic Release Inventory (TRI) as modeled by CalTOX, a multimedia multipathway fate and exposure model. Risks were then translated into social costs using cancer willingness to pay. For a baseline emissions year of 1998, 260 excess cancer cases were calculated for 116 TRI chemicals, dominated by ingestion risk from polycyclic aromatic compounds and dioxins emitted by the primary aluminum and cement industries, respectively. The direct emissions of a small number of industry sectors account for most of the U.S. population cancer risk. For the majority of industry sectors, however, cancer risk per $1 million output is associated with supply chain upstream emissions. Ranking industries by total (direct + upstream) supply chain risk per economic output leads to different conclusions about the relative hazards associated with these industries than a conventional ranking based on emissions per economic output.

Threatened fishes of the world: Noturus munitus Suttkus & Taylor 1965 (Ictaluridae) - Micah G. Bennett; D. Albrey. Arrington; Bernard R. Kuhajda; Thomas E. Shepard (Environmental Biology of Fishes, 2005)

The application of prescribing indicators to a primary care prescription database in Ireland - D. Williams; K. Bennett; J. Feely (European Journal of Clinical Pharmacology, 2005)

Looking to the Future of Ecosystem Services - E. M. Bennett; G. D. Peterson; E. A. Levitt (Ecosystems, 2005)

Numerical analysis of surface and fossil pollen spectra from northern Fennoscandia - K. D. Bennett; S. Hicks (Journal of Biogeography, 2005)
Aim Determination of the main directions of variance in an extensive data base of annual pollen deposition, and the relationship between pollen data from modified Tauber traps and palaeoecological data. Location Northern Finland and Norway. Methods Pollen analysis of annual samples from pollen traps and contiguous high‐resolution samples from a peat sequence. Numerical analysis (principal components analysis) of the resulting data. Results The main direction of variation in the trap data is due to the vegetation region in which each trap is located. A secondary direction of variation is due to the annual variability of pollen production of some of the tree taxa, especially Betula and Pinus . This annual variability is more conspicuous in ‘absolute’ data than it is in percentage data which, at this annual resolution, becomes more random. There are systematic differences, with respect to peat‐forming taxa, between pollen data from traps and pollen data from a peat profile collected over the same period of time. Main conclusions Annual variability in pollen production is rarely visible in fossil pollen samples because these cannot be sampled at precisely a 12‐month resolution. At near‐annual resolution sampling, it results in erratic percentage values which do not reflect changes in vegetation. Profiles sampled at near annual resolution are better analysed in terms of pollen accumulation rates with the realization that even these do not record changes in plant abundance but changes in pollen abundance. However, at the coarser temporal resolution common in most fossil samples it does not mask the origin of the pollen in terms of its vegetation region. Climate change may not be recognizable from pollen assemblages until the change has persisted in the same direction sufficiently long enough to alter the flowering (pollen production) pattern of the dominant trees.

Characterization of the active site and insight into the binding mode of the anti-angiogenesis agent fumagillin to the manganese(II)-loaded methionyl aminopeptidase from Escherichia coli - Ventris M. D’souza; Robert S. Brown; Brian Bennett; Richard C. Holz (JBIC Journal of Biological Inorganic Chemistry, 2005)

The Holocene spread of Picea abies (L.) Karst. in Fennoscandia and adjacent areas - Thomas Giesecke; K. D. Bennett (Journal of Biogeography, 2004)
Aim The Holocene spread of Picea abies in Fennoscandia is well established from many sites and thus provides an opportunity for detailed study of the dynamics of tree spread and population expansion. Early‐ and mid‐Holocene macrofossil evidence for presence of P. abies in Fennoscandia has questioned traditional interpretations of the timing and direction of its spread. This paper aims to determine when, from where and by which pathways P. abies spread into Fennoscandia. Understanding the character and dynamics of this spread may give insight into the general understanding of Holocene tree spread. Location The north‐western distribution of P. abies in Europe, including Norway, Sweden, Finland, Estonia, Latvia, Lithuania, north‐western Russia, parts of Byelorussia and Poland. Methods Holocene pollen diagrams with independent dating control were collected from this region. The timing of the onset of the continuous curve, the timing of the rise of the curve, the first appearance of frequencies of 1%, 3%, 5%, and 10%, as well as timing and the maximum amount of P. abies pollen, was obtained from these pollen diagrams. A GIS analysis was used to display the data and interpolate ages over the area under investigation. Results Maps are presented showing a clear ESE to WNW trend in the spread of P. abies for all characters interpolated. The timing of the rise of the curve was difficult to use as sites east of the Baltic have slowly rising P. abies frequencies while the western sites often show a rapid rise. Main conclusions The spread of P. abies in Fennoscandia and adjacent areas can be separated into two phases: (i) A rapid early Holocene spread out of Byelorussia and northern Russia at low population density giving rise to small outpost populations, possibly as far west as the Scandes Mountains. (ii) A mid‐ to late Holocene front‐like spread at high population densities moving from east to west into the Baltic Republics and Finland, into northern Scandinavia and then moving south and west towards its present‐day distributional limits.

The conservation of the belted beauty Lycia zonaria britannica (Lepidoptera, Geometridae) in the United Kingdom - M.A. Howe; D. Hinde; D. Bennett; S. Palmer (Journal of Insect Conservation, 2004)

(2R,7S)-Diacetoxytridecane: Sex Pheromone of the Aphidophagous Gall Midge, Aphidoletes aphidimyza - Man-Young Choi; Grigori Khaskin; Regine Gries; Gerhard Gries; Bernard D. Roitberg; David A. Raworth; Doo-Ho Kim; Robb G. Bennett (Journal of Chemical Ecology, 2004)

Influence of material deprivation on prescribing patterns within a deprived population - D. Williams; C. Teljeur; K. Bennett; A. Kelly; J. Feely (European Journal of Clinical Pharmacology, 2003)

Acute Toxicity of Methyl-Parathion in Wetland Mesocosms: Assessing the Influence of Aquatic Plants Using Laboratory Testing with Hyalella azteca - R. Schulz; M. T. Moore; E. R. Bennett; C. D. Milam; J. L. Bouldin; J. L. Farris; S. Smith; C. M. Cooper (Archives of Environmental Contamination and Toxicology, 2003)

[3H]-thymidine labelling of DNA triggers apoptosis potentiated by E1A-adenoviral protein - S. N. Orlov; D. V. Pchejetski; S. Der Sarkissian; V. Adarichev; S. Taurin; A. V. Pshezhetsky; J. Tremblay; G. V. Maximov; D. deBlois; M. R. Bennett; P. Hamet (Apoptosis, 2003)

Effect of saline intake on water flux and osmotic homeostasis in Pekin ducks (Anas platyrhynchos) - D. Bennett; D. Gray; M. Hughes (Journal of Comparative Physiology B, 2003)

Effect of saline acclimation on body water and sodium compartmentalization in Pekin ducks (Anas platyrhynchos) - D. Bennett; D. Kojwang; T. Sullivan; D. Gray; M. Hughes (Journal of Comparative Physiology B, 2003)

Comment: Formation and reorientation of structure in the surge‐type glacier Kongsvegen, Svalbard J. Woodward, T. Murray and A. Mc Caig (2002) Journal of Quaternary Science 17 : 201–209 - N. F. Glasser; M. J. Hambrey; M. R. Bennett; D. Huddart (Journal of Quaternary Science, 2003)

Differential distribution of interneurons in the neural networks that control walking in the mudpuppy (Necturus maculatus) spinal cord - J. Cheng; K. Jovanovic; Y. Aoyagi; D. J. Bennett; Y. Han; R. B. Stein (Experimental Brain Research, 2002)

Electrophoretic variation as a measure of speciesdifferentiation between four species of the genus Lolium - Sarita Jane Bennett; Mike D. Hayward; Dave F. Marshall (Genetic Resources and Crop Evolution, 2002)

Molecular systematics of Solanum section Lycopersicum (Lycopersicon) using the nuclear ITS rDNA region - J. A. Marshall; S. Knapp; M. R. Davey; J. B. Power; E. C. Cocking; M. D. Bennett; A. V. Cox (Theoretical and Applied Genetics, 2001)

Non-erythroid form of acute intermittent porphyria caused by promoter and frameshift mutations distant from the coding sequence of exon 1 of the HMBS gene - Sharon D. Whatley; Andrew G. Roberts; David H. Llewellyn; Christopher P. Bennett; Christine Garrett; George H. Elder (Human Genetics, 2000)

Effect of global atmospheric carbon dioxide on glacial–interglacial vegetation change - K. D. Bennett; K. J. Willis (Global Ecology and Biogeography, 2000)
Global vegetation changes at the time‐scale of the Earth's orbital variations (10 4 –10 5 years) have been interpreted as a direct effect of consequential climatic changes, especially temperature. At mid‐ and high latitudes, the evidence from fossil data and general circulation models (GCMs) supporting this hypothesis is strong, but at low latitudes there is a major discrepancy. GCMs predict temperature changes that are less than those inferred from palaeoclimatic data, including the plant fossil record. However, changes in atmospheric CO 2 concentrations can account for a high proportion of the low‐latitude vegetation change hitherto attributed to temperature change, and may thus explain the discrepancy. The implications of this finding are considerable for understanding patterns of macroevolution and ecosystem development throughout the geological record.

Avian colour vision and avian video playback experiments - I. C. Cuthill; N. S. Hart; J. C. Partridge; A. T. D. Bennett; S. Hunt; S. C. Church (acta ethologica, 2000)

Improvement of nutritional site quality 13 years after single application of fertiliser N and P on regenerating cedar-hemlock cutovers on northern Vancouver Island, B.C. - Robert L. Bradley; Brian D. Titus; Caroline M. Preston; Jennifer Bennett (Plant and Soil, 2000)

Visual pigments, oil droplets, ocular media and cone photoreceptor distribution in two species of passerine bird: the blue tit ( Parus caeruleus L.) and the blackbird ( Turdus merula L.) - N. S. Hart; J. C. Partridge; I. C. Cuthill; A. T. D. Bennett (Journal of Comparative Physiology A, 2000)

Isolation of genes predominantly expressed in guard cells and epidermal cells of Nicotiana glauca - Lawrence B. Smart; Kimberly D. Cameron; Alan B. Bennett (Plant Molecular Biology, 2000)

Preparation of radiolabelled very-low-density lipoprotein in high yield by extended rat liver perfusion - Mark J. Bennett; David Hauton; David G. Hole; Rhys D. Evans (Biotechnology Letters, 2000)

Meta-igneous (non-gneissic) tonalites and quartz-diorites from an extensive ca. 3800 Ma terrain south of the Isua supracrustal belt, southern West Greenland: constraints on early crust formation - Allen P. Nutman; Vickie C. Bennett; Clark R. L. Friend; Marc D. Norman (Contributions to Mineralogy and Petrology, 1999)

Stereoselective Pharmacokinetics and Pharmacodynamics of Propylisopropyl Acetamide, a CNS-Active Chiral Amide Analog of Valproic Acid - Ofer Spiegelstein; Boris Yagen; René H. Levy; Richard H. Finnell; Gregory D. Bennett; Michael Roeder; Volker Schurig; Meir Bialer (Pharmaceutical Research, 1999)

Interactive effects of subanesthetic ketamine and haloperidol in healthy humans - John H. Krystal; D. Cyril D'Souza; Laurence P. Karper; Alexandre Bennett; Anissa Abi-Dargham; Danielle Abi-Saab; Karyn Cassello; M. B. Bowers Jr.; Sally Vegso; George R. Heninger; Dennis S. Charney; M. B. Bowers (Psychopharmacology, 1999)

Antisense suppression of tomato endo-1,4-β-glucanase Cel2 mRNA accumulation increases the force required to break fruit abscission zones but does not affect fruit softening - David A. Brummell; Bradford D. Hall; Alan B. Bennett (Plant Molecular Biology, 1999)

Self-administration of cocaine analogs by rats - D. C. S. Roberts; Rachel Phelan; L. Mark Hodges; Melinda M. Hodges; Barbara Bennett; Steve Childers; Huw Davies (Psychopharmacology, 1999)

Indole glucosinolate and auxin biosynthesis in Arabidopsis thaliana (L.) Heynh. glucosinolate mutants and the development of clubroot disease - Jutta Ludwig-Müller; Kerstin Pieper; Manfred Ruppel; Jerry D. Cohen; Ephraim Epstein; Guy Kiddle; Richard Bennett (Planta, 1999)

Electrophoretic differentiation in isolated populations of Lolium rigidum Gaud. - S. J. Bennett; M. D. Hayward (Molecular Ecology, 1999)
Sixteen wild populations of Lolium rigidum Gaud. were collected from island and mainland locations in Mediterranean Europe and western Asia. Five loci, controlling isozymes at four enzyme systems, were assayed on 60 plants per population using starch gel electrophoresis. Gene diversity measures and Nei’s genetic distance were calculated, and the relationships between the populations were analysed using principal component (PCA) and cluster analyses. All populations were found to show a gene diversity index that is consistent with that expected in a cross‐fertilising species. The highest gene diversity measures were recorded in some of the island populations. Both PCA and cluster analysis grouped the Balearic Island populations together and separated the Spanish and Sardinian populations from any of the others. The results are discussed with respect to a number of theories of migration between populations, and in relation to the colonization history of each island. It is suggested that the preservation of these island populations in gene banks is important as part of a core collection of the species.

Identification and characterization of the murine FK506 binding protein (FKBP) 12.6 gene - Jane A. Bennett; Yevette C. Clancy; John D. McNeish (Mammalian Genome, 1998)

Tetrachromacy, oil droplets and bird plumage colours - M. Vorobyev; D. Osorio; A. T. D. Bennett; N. J. Marshall; I. C. Cuthill (Journal of Comparative Physiology A, 1998)

Influence of Gravity on Cardiac Performance - George M. Pantalos; M. Keith Sharp; Stewart J. Woodruff; D. Sean O’Leary; Richard Lorange; Scott D. Everett; Thomas E. Bennett; Thomas Shurfranz (Annals of Biomedical Engineering, 1998)

Nine new dog DLA-DRB1 alleles identified by sequence-based typing - L. J. Kennedy; Stuart D. Carter; Annette Barnes; Susan Bell; David Bennett; William E. R. Ollier; Wendy Thomson (Immunogenetics, 1998)

Detection of Bacteraemia in Patients with Fever and Neutropenia Using 16S rRNA Gene Amplification by Polymerase Chain Reaction - B. E. Ley; C. J. Linton; D. M. C. Bennett; H. Jalal; A. B. M. Foot; M. R. Millar (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Sequence Comparison of Avian Infectious Bronchitis Virus S1 Glycoproteins of the Florida Serotype and Five Variant Isolates from Georgia and California - Kristi M. Moore; Joyce D. Bennett; Bruce S. Seal; Mark W. Jackwood (Virus Genes, 1998)

Does Lepidopteran Larval Crypsis Extend into the Ultraviolet? - Stuart C. Church; Andrew T. D. Bennett; Innes C. Cuthill; Sarah Hunt; Nathan S. Hart; Julian C. Partridge (The Science of Nature, 1998)

Detection of bacteraemia in patients with fever and neutropenia using 16S rRNA gene amplification by polymerase chain reaction - B. E. Ley; C. J. Linton; D. M. C. Bennett; H. Jalal; A. B. M. Foot; M. R. Millar (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Interactive effects of subanesthetic ketamine and subhypnotic lorazepam in humans - John H. Krystal; Laurence P. Karper; Alexandre Bennett; D. Cyril D'Souza; Anissa Abi-Dargham; Kristen Morrissey; Danielle Abi-Saab; J. Douglas Bremner; M. B. Bowers Jr.; Raymond F. Suckow; Philip Stetson; George R. Heninger; et al. (Psychopharmacology, 1998)

Announcement - P. D. Markel; B. Bennett; M. A. Besson; L. Gordon; V. J. Simpson; T. E. Johnson (Mammalian Genome, 1997)

Erratum - P. D. Markel; B. Bennett; M. A. Besson; L. Gordon; V. J. Simpson; T. E. Johnson (Mammalian Genome, 1997)

Homoeologous pairing and recombination in backcross derivatives of tomato somatic hybrids [Lycopersicon esculentum (+) L. peruvianum] - A. S. Parokonny; J. A. Marshall; M. D. Bennett; E. C. Cocking; M. R. Davey; J. Brian Power (Theoretical and Applied Genetics, 1997)

Mercury Residues in South Florida Apple Snails ( Pomacea paludosa ) - J. D. Eisemann; W. N. Beyer; R. E. Bennetts; A. Morton (Bulletin of Environmental Contamination and Toxicology, 1997)

Perceptions of Species Abundance, Distribution, and Diversity: Lessons from Four Decades of Sampling on a Government-Managed Reserve - J. Whitfield Gibbons; Vincent J. Burke; Jeffrey E. Lovich; Raymond D. Semlitsch; Tracey D. Tuberville; J. Russell Bodie; Judith L. Greene; Peter H. Niewiarowski; Howard H. Whiteman; David E. Scott; Joseph H. K. Pechmann; Christopher R. Harrison; et al. (Environmental Management, 1997)

Alginate Encapsulation of the White Rot Fungus Phanerochaete chrysosporium - A.K. Loomis; A.M. Childress; D. Daigle; J.W. Bennett (Current Microbiology, 1997)

Polymerase chain reaction for detection of herpesvirus simiae (B virus) in clinical specimens - M. J. Slomka; D. W. G. Brown; J. P. Clewley; A. M. Bennett; L. Harrington; D. C. Kelly (Archives of Virology, 1993)

Identification and sequence determination of the capsid protein gene of feline calicivirus - M. J. Carter; I. D. Milton; P. C. Turner; J. Meanger; M. Bennett; R. M. Gaskell (Archives of Virology, 1992)

Characterization of orthopoxviruses isolated from feline infections in Britain - J. Naidoo; D. Baxby; M. Bennett; R. M. Gaskell; C. J. Gaskell (Archives of Virology, 1992)

Growth and yield of potato (Solanum tuberosum L.) cultivars Atlantic and Monona as influenced by seed type and size - Matthew D. Kleinhenz; Mark A. Bennett (American Journal of Potato Research, 1992)

Studies on poxvirus infection in cats - M. Bennett; R. M. Gaskell; C. J. Gaskell; D. Baxby; D. F. Kelly (Archives of Virology, 1989)

The computation of structure from fixed-axis motion: Rigid structures - D. D. Hoffman; B. M. Bennett (Biological Cybernetics, 1988)

Allorhogas pyralophagus [Hym.: Braconidae], a gregarious external parasite imported into texas, USA, for biological control of the stalkborerEoreuma loftini [Lep.: Pyralidae] on sugar cane - J. W. Smith; H. W. Browning; F. D. Bennett (BioControl, 1987)

The computation of structure from fixed-axis motion: rigid structures - D. D. Hoffman; B. M. Bennett (Biological Cybernetics, 1986)

The computation of structure from fixed-axis motion: Nonrigid structures - B. M. Bennett; D. D. Hoffman (Biological Cybernetics, 1985)

Genome size and the proportion of repeated nucleotide sequence DNA in plants - R. B. Flavell; M. D. Bennett; J. B. Smith; D. B. Smith (Biochemical Genetics, 1974)

Plagiprospherysa trinitatis [Dipt.: Tachinidae], A parasite ofElasmopalpus lignosellus [Lep.: Phycitidae] in Trinidad, W. I. - M. N. Beg; F. D. Bennett (BioControl, 1974)

Biological control ofDiatraea saccharalis (F.) in Barbados byApanteles flavipes Cam. andLixophaga Diatraeae T. T. - M. M. Alam; F. D. Bennett; K. P. Carl (BioControl, 1971)

Current status of biological control of the small moth borers of sugar caneDiatraea spp. [Lep. Pyraeididae] - F. D. Bennett (BioControl, 1971)

The development of an attenuated foot-and-mouth disease virus vaccine by modification and cloning in tissue cultures of BHK 21 cells - G. N. Mowat; D. A. Barr; J. H. Bennett (Archives of Virology, 1969)

The use of interferon production as a marker in the development of a modified strain of foot-and-mouth disease virus - R. F. Sellers; G. N. Mowat; J. H. Bennett; D. A. Barr (Archives of Virology, 1968)

Biological control ofOpuntia spp. byCactoblastis cactorum in the Leeward Islands (West Indies) - F. J. Simmonds; F. D. Bennett (BioControl, 1966)

Studies on the life history and biological control of the spittlebug,Clastoptera undulata uhler (Cercopidae: Hemiptera) - F. D. Bennett; I. W. Hughes (BioControl, 1963)

Sectional notes - L. M. Ware; E. Marx; M. A. Lindsay; C. H. Metzger; H. L. Cochran; E. R. Bennett; A. C. Moreau; Frank W. Hussey; H. A. Reiley; Marx Koehnke; J. C. Campbell; M. E. Gardner; et al. (American Journal of Potato Research, 1943)

Sectional notes - C. H. Metzger; E. R. Bennett; W. B. Ward; J. G. Richard; Ralph W. Donaldson; T. M. Patterson; L. Harris; Marx Koehnke; J. M. Jenkins; W. H. Martin; Robert Schmidt; E. M. Gillig; et al. (American Journal of Potato Research, 1937)

Sectional notes - B. A. Brown; E. R. Bennett; W. B. Ward; Ralph W. Donaldson; Marx Koehnke; Wm. H. Martin; K. W. Lauer; T. E. Odland; H. L. Bailey; Chas D. Gaines; J. G. Milward (American Journal of Potato Research, 1936)

Sectional notes - E. R. Bennett; Ralph W. Donaldson; A. G. Tolaas; Marx Koehnke; Dan A. O’Brien; W. H. Martin; E. V. Hardenburg; Robert Schmidt; E. B. Tussing; T. E. Odland; Brooks D. Drain; J. G. Milward (American Journal of Potato Research, 1936)

Sectional notes - H. W. Poulsen; W. B. Ward; E. R. Bennett; C. L. Fitch; E. L. Nedwick; Ralph W. Donaldson; A. G. Tolaas; E. E. Isaac; H. O. Werner; E. V. Hardenburg; G. K. Middlenton; E. M. Gillig; et al. (American Journal of Potato Research, 1935)

Sectional notes - J. H. Heckman; H. G. Zuckerman; C. H. Metzger; B. A. Brown; E. R. Bennett; W. B. Ward; C. L. Fitch; O. H. Elmer; Jhon S. Gardner; Julan C. Miller; Frank W. Hussey; E. L. Newdick; et al. (American Journal of Potato Research, 1935)